Computational Investigation of Dicyanoisophorone-Based Fluorophores: Substituent and Site Effects - Yating Ding; Zhengze Zhang; Rui Wu; Ying Xu; Qu Zhang; Zhao Liu; Junqiang Lei (Journal of Fluorescence, 2025)

3D skeletonization and phenotyping for soybean root system architecture using a bio-inspired algorithm - Xuehai Zhou; Tianzi Yang; Rui Xu; Alexander Bucksch; Pierre Dutilleul; Davoud Torkamaneh; Shangpeng Sun (Computers and Electronics in Agriculture, 2025)

A novel dual-polarization SAR vegetation index for crop phenology detection - Xin Bao; Rui Zhang; Xu He; Age Shama; Gaofei Yin; Jie Chen; Hongsheng Zhang; Guoxiang Liu; Xianjian Shi (Computers and Electronics in Agriculture, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Urinary metal mixtures and cataract: Findings from a U.S. population-based study and network pharmacology analysis - Runzi Yang; Jing Li; Rui Liu; Tingting Ren; Nan Wang; Liangyuan Xu; Jianmin Ma (Toxicology Letters, 2025)

Combined inhibition of WEE1 by AZD1775 synergistically enhances CX-5461 mediated DNA damage and induces cytotoxicity in glioblastoma - Meng Cheng; Rui Wang; Ying Pang; Xu Chen; Jing Zhang; Chunlong Zhong (Tissue and Cell, 2025)

Exploratory landscape analysis on black-box optimization problems via Graph Neural Network - Xu Yang; Rui Wang; Kaiwen Li; Wenhua Li; Tao Zhang (Swarm and Evolutionary Computation, 2025)

Dynamic response and liquefaction mitigation of immersed tunnels under seismic loads: A coupled seawater-seabed-tunnel analysis - Weiyun Chen; Zhiqiang Luo; Lingyu Xu; Yewei Zheng; Lei Su; Rui Huang (Soil Dynamics and Earthquake Engineering, 2025)

Spatio-temporal variations of soil particle size distribution under wind erosion in a temperate grassland: A seven-year landscape scale revisited analysis - Yuxin Feng; Zhuodong Zhang; Zhuoli Zhou; Bo Chen; Ying Li; Xinyu Zou; Rui Xu; Shuran Gao (Soil and Tillage Research, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

900 Wh L–1 lithium-ion batteries enabled by self-assembled copolymer induced built-in electric field on graphite anode - Yumeng Zhao; Changdong Li; Dehua Xu; Rui Li; Bin Han; Xinlian Chen; Bohua Wen; Haimei Xie; Aoxuan Wang; Jiayan Luo (Science Bulletin, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

Interaction of secreted protein PgSLP and citrus calmodulin-like protein CsCML27/44 in fruit disease defense - Yao Xu; Ou Chen; Rong Zhu; Rui Huang; Jian Ming; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Value decomposition reinforcement learning-based formation control for multi-USVs with incomplete information - Rui Xiao; Chun Liu; Hongtian Chen; Liang Xu; Youmin Zhang (Ocean Engineering, 2025)

Ship manoeuvring model identification using mutual information clustering with stepwise regression structural optimisation under small-sample constraints - Xiufeng Zhang; Rui Tian; Haitong Xu; Xiuwen Liu; C. Guedes Soares (Ocean Engineering, 2025)

The efficient removal of dolomite from phosphate ores using a novel collector: Flotation selectivity and collecting mechanism - Yifan Zhang; Yudi Yan; Bingqiao Yang; Rui Ma; Yang Xu; Huihua Luo; Fang Zhou (Minerals Engineering, 2025)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Factors affecting micro(nano)plastic release during intravenous therapy: Direct blood exposure - Haoming Xu; Penghui Li; Yujian Lai; Sujuan Yu; Rui Liu; Guomao Zheng; Bintian Zhang; Qian Sun; Jingfu Liu (Journal of Hazardous Materials, 2025)

Response of microbial communities in capillary zone to toluene natural attenuation under leaching/capillary rise - Jiawei Liu; Rui Zuo; Guanlan Wu; Qiao Li; Donghui Xu; Tianfei Chen; Jingchao Liu; Ziyi Wu; Jinsheng Wang (Journal of Hazardous Materials, 2025)

Resilient polyurea barriers for copper smelting wastewater containment: Synergistic effects of microstructural optimization and heavy metal immobilization - Feng Chen; Linhai Ye; Wenchang Li; Rui Xiang; Youcai Zhao; Qifei Huang; Ya Xu (Journal of Cleaner Production, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Stability and durability of polymeric membranes in membrane bioreactors for industrial wastewater treatment - Qingxian Su; Yijie Zhong; Joceleen Chin Jia Rui; Meiyue Ding; Tze Chiang Albert Ng; Boyan Xu; How Yong Ng (Journal of Environmental Chemical Engineering, 2025)

Confinement engineering of Co@C nanocages in 3D g-C3N4 scaffolds boosts photothermal CO2-to-fuel conversion - Yanan Wang; Jingjie Li; Rui Zhang; Tingting Xu; Chenlu Li; Jie Ma; Han Li; Liwei Lin; Song Xu; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Study on intracellular detoxification mechanisms of Aspergillus sydowii under cadmium stress - Longteng Zhi; Yutong Liu; Rui Xu; Jingyan Guo; Hongyan Yu; Yue Teng (Journal of Environmental Management, 2025)

All-solid-waste-based non-sintered ceramsite prepared from coal fly ash and dechlorinated municipal solid waste incineration fly ash: performance and hydration mechanisms - Kai Xu; Xinyuan Zhan; Yan Wang; Jie Wang; Rui Deng; Rui Wang; Chen Li; Shui Jiang; Xiaomoli Li; Jingyu Li; Yuxi Zhang (Journal of Environmental Management, 2025)

Degradation of trichloroethylene by magnetite-activated periodate and the effect of humus on the degradation mechanism - Jiayuan Li; Shibing Jia; Lei Chen; Rui Song; Hongyong Wang; Gang Xu (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Characterization of key aroma-active compounds in soy sauce “Guoqi” after Chinese cooking by GC×GC-O-MS - Rui Xu; Baosong Wang; Huijuan Sun; Huanlu Song (International Journal of Gastronomy and Food Science, 2025)

Effects of representative Chinese cattle breeds on the eating quality and microstructure of braised beef - Jian Hu; Xiaoke Fu; Yijie Cai; Ronglan Wang; Rui Xu; Chengrong Zheng; Xing Chen; Bowen Yan (International Journal of Gastronomy and Food Science, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Toward structured and functional salted egg yolks: Role of calcium chloride concentration on protein conformation, aggregation, and gel formation under sodium chloride dry-curing - Jian Li; Rui Chuang; Jiayu Liang; Huajiang Zhang; Lina Xu; Ying Ma; Ning Xia; Yonggang Tu; Ahmed M. Rayan; Mohamed Ghamry (Food Research International, 2025)

Mechanism of TGase-induced oyster peptide-chitosan oligosaccharide glycosylation and amelioration effects of its zinc complex on zinc deficiency-associated neuron damages and oxidative stress - Xuening Yu; Rui Liu; Yuewen Xu; Ningning Pan; Xiaoyang Liu; Yoshimasa Nakamura; Dayong Zhou (Food Research International, 2025)

Incorporation of purified betacyanin-rich extract from Hylocereus polyrhizus peel into bread and its impacts on dough properties, bread baking quality, and nutritional attributes - Xiaojuan Xu; Serena Wong Mun Rui; Yingfen Jiang; Kelly Natalia Djohari; Weibiao Zhou (Food Chemistry, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Comparative analysis on antioxidant capacity, immunity and histopathological changes of largemouth bass (Micropterus salmoides) in response to mono- or co-infection with Aeromonas veronii and Nocardia seriolae - Gaofeng Cheng; Nengbin Zhu; Ruiping Xu; Eakapol Wangkahart; Lin Zhang; Lihe Liu; Rui Wang; Zhen Xu; Weiguang Kong; Hongsen Xu (Fish & Shellfish Immunology, 2025)

Soil pH and organic phosphorus co-shape the diversity and assembly processes of arbuscular mycorrhizal fungal community in subtropical broadleaved forests - Rui Xu; Zhucheng Yu; Yang Liu; Yidan Liu; Xingcong Ma; Xiaomin Ma; Wenhao Jin; Yongfu Li; Junhui Chen; Hua Qin (European Journal of Soil Biology, 2025)

Airway exposure to microplastics: Potential mechanisms from epithelial barrier damage to the development of allergic rhinitis - Xu Zhang; Mengyuan Liu; Zhiqiang Zhang; Xinyu Huang; Daoming Bai; Rui Yang; Maohua Wang; Peng Wang; Chunping Yang (Environmental Research, 2025)

Recent advances in manganese-based materials for water remediation: Multipollutant adsorption and catalytic oxidation - Hanghang Wang; Guangfei Qu; Yingying Cai; Chenyang Yin; Yaxin Tian; Rui Xu; Xinxin Liu; Minjie He; Changyi He; Jiao Wei (Environmental Research, 2025)

Fracture behavior of heterogeneous layered sandstone under mixed loading after thermal treatment: A thermal–mechanical grain-based FDEM model - Wei Kuang; Tengfei Guo; Xu Chang; Yichao Rui (Computers and Geotechnics, 2025)

Integrated untargeted metabolomics and physiological analysis reveal the response mechanisms of Procambarus clarkii larvae to carbonate alkalinity exposure - Kun Guo; Zhigang Zhao; Rui Zhang; Liang Luo; Shihui Wang; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Detection of neutralizing antibody to Feline herpesvirus type 1 in cat serum - Jia Yang; Rui Mei; Kangyixin Sun; Fuqiang Xu; Fan Jia (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Spatiotemporally controlled intelligent hydrogel platform for precision RNA interference therapy in lumbar facet joint osteoarthritis - Chongzhi Pan; Shuihua Ding; Linfeng He; Xiang Luo; Le Liao; Jian Zhang; Rui Ding; Peichuan Xu; Huajun Pan; Xinxin Miao; Xigao Cheng (Chemical Engineering Journal, 2025)

Atmospheric and room-temperature plasma mutagenesis enhances the tolerance of Arthrospira platensis to photoinhibition and high-CO2 levels - Ruolan Yuan; Chunli Yu; Rui Xu; Jin Liu; Lina Zhou; Shengxi Shao; Jun Qian; Jingjing Li; Peilun Xu; Wenguang Zhou (Chemical Engineering Journal, 2025)

Synergistic lattice engineering and surface passivation via cerium modification for robust ultrahigh-nickel layered oxide cathodes - Lunhao Deng; Rui Zhou; Jie Chen; Xiaotian Xu; Yuanyuan Chen; Xinyu Zhao; Liang Luo; Wang Xiang; Xiangwan Lai; Yingjie Zhang; Xianshu Wang; Ding Wang; et al. (Chemical Engineering Journal, 2025)

Metal-bridged self-assembly of recognition-functionalized MCOFs for ultrasensitive photoelectrochemical sensing of perfluorooctanoic acid - Xionghui Ma; Wenwen Cao; Rui Chen; He Yu; Chaohai Pang; Zhongsheng Yi; Yuhao Xiong; Bingjun Han; Zhi Xu; Jianping Li; Shuhuai Li (Chemical Engineering Journal, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

Process intensification of CO2 desorption by Higee technology: An industrial case study - Han-Zhuo Xu; Rui-Qi Jia; Yong Cai; Liang-Liang Zhang; Fei Gao; Guang-Wen Chu (Chemical Engineering Journal, 2025)

Carbon-modulated DPAOs metabolism drives high-rate denitrifying phosphorus removal with nitrate as the Electron acceptor in granular sludge systems - Rui Du; Duanyuan Xu; Xinpeng Xi; Shenbin Cao; Yongzhen Peng (Chemical Engineering Journal, 2025)

Dual pH/glutathione-responsive polyphenol-based self-assembled nanoparticles loaded with lambda-cyhalothrin show enhanced UV stability and non-target organism safety - Lei Wang; Zheng Zhang; Yu Fang; Rui Zhao; Shouhe Pan; Meng Yu; Yinjie Ma; Yinmin Wang; Xiquan Ding; Xinyu Guo; Fengyu Li; Pengkun Yan; et al. (Chemical Engineering Journal, 2025)

3D printed hydrogel with fingerprint-inspired features for enhanced sensing performance in electronic skin - Jianshe Hao; Yanbin Xu; Chaofan Yang; Rui Guo; Yang Lyu; Zhongying Ji; Xiaolong Wang (Chemical Engineering Journal, 2025)

Single-cell–guided repositioning of Sorafenib enables nano-immunotherapy for scarless burn healing - Yue Tao; Huaxin Li; Jiaheng Xie; Rui Ding; Zhiwei Zhuang; Xu Yang; Yang Zhu; Jie Shan; Xu-lin Chen (Chemical Engineering Journal, 2025)

Defect-mediated dual role interfaces enables the sulfur reduction reaction kinetics for highly stable lithium sulfur batteries - Xinmeng Li; Jiafeng Zhu; Rui Sheng; Tianmei Xu; Kai Chen; Juan Ding; Yudai Huang (Chemical Engineering Journal, 2025)

Start-up and operational strategies for side-stream nitrification reactors in a cyclic up-concentration nitrogen recovery process: Enhancing targeted nitrate conversion and deciphering nitrogen metabolism - Molin Lian; Zihang Ma; Guang Chen; Xiangdong Xu; Rui Tang; Shikun Yan; Yu Wang; Yuyue Zhang; Zhen Zhou (Chemical Engineering Journal, 2025)

Recent advances and perspectives in coordination polymer-based fluorescent sensors for vitamin detection - Zi-Hao Zhao; Zhi-Wei Liu; Xin-Rui Xu; Qian-Yu Yang; Zhao-Yang Tong (Chemical Engineering Journal, 2025)

A hierarchically porous AgNW-TPU composite with “pores-in-pore” architecture for bifunctional flexible sensors and energy harvesters - Rui Tao; Yang Feng; Cong Chang; Chengding Gu; Chuncai Shan; Xu Zhang; Yongyun Mao (Chemical Engineering Journal, 2025)

Chitosan-derived nanoemulsion enriched with Streptomyces metabolites for target control of tobacco leaf spot, enhanced foliar retention and plant nutrition - Xue Han; Chunli Xu; Rui Yang; Dan Chen; Yaning Li; Beibei Ge (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Sustainable arsenic stabilization method for hazardous As Ca residues using magnetite tailings and carbide slag for scorodite formation: Implications for harmless treatment and waste reduction - Rui Su; Xuedi Wang; Miao Xu; Yuyin Ma; Yanjiao Gao; Xu Ma; Yubo Cui; Chunxue Bai; Shaofeng Wang (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Integrated physical–chemical mechanisms drive carbon stabilization under conservation tillage in Karst agroecosystems - Guang Xu; Qishun Mo; Zhou Li; Wangfei Qin; Rui Dong; Xuechun Zhao; Chao Chen; Anna Gunina; Narasinha Shurpali; Tulasi Lakshmi Thentu; Gang Nie; Yuan Li (CATENA, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

Integration of transcriptome and metabolome analysis reveals that alternative splicing of TT8 modulates anthocyanin biosynthesis in postharvest blood orange stored at moderate temperature - Wang Jianhui; Xu Rui; Guo Weiqing; Li Zhihong; Liu dayu; Li Jingjing; Li Dagang; Chen Ying (Plant Molecular Biology, 2025)

Interplay between Nrf2 and ROS in regulating epithelial-mesenchymal transition: implications for cancer metastasis and therapy - Yi Xu; Shuning Hu; Rui Chen; Sheng Xu; Guangyang Yu; Lili Ji (Molecular Biology Reports, 2025)
Epithelial-mesenchymal transition (EMT), including developmental (Type I), wound healing (Type II), and pathological (Type III) subtypes, constitutes a critical driver of cancer metastasis. This review analyzes the redox interplay between nuclear factor erythroid 2-related factor 2 (Nrf2) and reactive oxygen species (ROS) in EMT regulation and cancer progression. Nrf2 maintains redox homeostasis through antioxidant gene activation while paradoxically promoting tumor survival and drug resistance via Keap1-dependent degradation and phosphorylation-mediated stabilization. ROS generated through mitochondrial and NADPH oxidase pathways exhibit dual functionality: moderate levels activate EMT transcription factors to drive metastasis and cancer stem cells (CSCs) plasticity, whereas excessive ROS induce apoptosis and ferroptosis. While Nrf2 typically suppresses EMT through ROS neutralization and epithelial integrity preservation, chronic Nrf2 activation in CSCs paradoxically sustains metastatic potential through redox buffering. This synthesis delineates the spatiotemporal regulation of Nrf2-ROS-EMT networks across tumor microenvironments, emphasizing therapeutic opportunities through redox balance modulation and pathway-specific Nrf2 inhibition in advanced malignancies.

Time trend of urine metal levels in preschool children in the electronic waste recycling area and its association with hemoglobin levels - Rongyi Kang; Jieting Chen; Kaihui Li; Rui Sun; Jian Zhang; Chenxu Dai; Xijin Xu; Bo Xie; William W. Au; Lei Tan; Xia Huo (International Archives of Occupational and Environmental Health, 2025)

CFD–DEM and Experimental Investigation of Seepage Behavior at Soil–Structure Interfaces - Xue-min Yang; Zeng-guang Xu; Jun-rui Chai; Cheng Cao; Chao-wei Sun; Gang Li (Geotechnical and Geological Engineering, 2025)

Multi-omics based consensus subtypes, development of prognostic signature, and identification of INHBB as a potential therapeutic target in colorectal cancer - Xu Wang; Yuanmin Xu; Rui Sun; Sheng Wang; Xiang Wei (Functional & Integrative Genomics, 2025)

Comparative pan-genome analysis of Huperzia and Phlegmariurus and transcriptomics reveals thermal adaptation in Huperzia - Muzi Li; Yazhu Wu; Haibo Li; Zhongnian Zhang; Rui Qin; Jiahao Wen; Yeqin Xu; Chengcheng Bao; Dekai Wang (Functional & Integrative Genomics, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

GSANet: research on EEG decoding based on graph attention and self attention in auditory attention detection - Yuanlin Dong; Rui Dai; Tiancheng Xie; Ke Xu; Liya Huang (Cognitive Neurodynamics, 2025)

Enhancing performance of SSVEP-based visual acuity via exploiting subject-specific information - Xiaowei Zheng; Boyu Wen; Xin Yan; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

Emotion recognition of CNN bidirectional long short-term memory with center and Softmax loss function (CNN-BiLSTM-CS) EEG -based - Xiaodan Zhang; Shuyi Wang; Yige Li; Kemeng Xu; Rui Zhao; Wei Wei (Cognitive Neurodynamics, 2025)

Classification for Alzheimer's disease and frontotemporal dementia via resting-state electroencephalography-based coherence and convolutional neural network - Rundong Jiang; Xiaowei Zheng; Jiamin Sun; Lei Chen; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

A review of the low-field NMR technique for analyzing the state of water in clayey soils - Yingyao Qin; Liang Wang; Xiaolong Ma; Yong Wan; Rui Xu; Houzhen Wei (Bulletin of Engineering Geology and the Environment, 2025)

The protective role of HINT2 in hypoxia injury of neuroblastoma cells and its regulatory mechanism on MCU-MICU1 pathway - Shao Rui; Zhang Lilong; Geng Yannan; Xu Tiantong (Neurophysiology, 2025)

Heavy Magnesium Isotope Evidence for a Key Role of Serpentinite-Derived Fluids in Arc Magmatism - Rui An; Yongsheng He; Shan Ke; Guochun Zhao; Aiying Sun; Yang Wang; Hongsheng Xu (Journal of Earth Science, 2025)

A systematic review of montmorillonite-asphalt composite materials: Green clay mineral-reinforced asphalt for sustainable pavement solutions - Hao Lai; Anhua Xu; Jianliang Zhai; Youjie Zong; Wei Deng; Haoyan Guo; Bowen Guan; Mingfeng Chang; Rui Xiong; Zhenjun Wang (Applied Clay Science, 2025)

Effects of Bacillus licheniformis supplementation on growth performance, intestinal health and oxidative stress in weaning transition male dairy calves - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Deep structure of the middle segment of the Bangong-Nujiang Suture Zone based on aerogravity and aeromagnetic anomalies, Qinghai-Tibet Plateau - Bao-bao Cao; Dao-qing Zhou; Yan-yan Wei; Rui Zhao; Qiao-juan Yan; Lei Xu; Di-shuo Zhang (Applied Geophysics, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Understanding orbital pacing, uplift dynamics, and oceanic influences in aeolian red clay sediments over the Chinese Loess Plateau through cyclostratigraphy insights - Xiaohao Wei; Rui Zhang; Vadim A. Kravchinsky; Joseph V. Ferraro; Jie Qin; Minghao Ma; Dongyue Zhang; Xiaojuan Li; Leping Yue; Jianxing Li; Yong Xu; Ji Ma; et al. (International Geology Review, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Formyl peptide receptor 2 (FPR2) mediates cisplatin-induced cochlear inflammation and hair cell apoptosis - Jiaojiao Hou; Rui Liang; Yuhan Lin; Daiyao Liu; Jiamei Li; Yifan Liu; Tao Xu; Shuangyue Liu; Aimei Wang (Toxicology, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Efficient degradation mechanism of fomesafen by earthworms and gut degrading bacteria synthetic community - Yan Ge; Aoqi Yang; Yongkang Dong; Siqi Wang; Rui Xu; Dongxing Zhou (Pesticide Biochemistry and Physiology, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Aerodynamic and structural Co-optimization of offshore wind turbine blades using a novel adaptive surrogate-based optimization method - Rui Meng; Xuhui Chen; Liangliang Chen; Nenggang Xie; Lu Wang; Bofeng Xu (Ocean Engineering, 2025)

Prediction method of propeller tip vortex cavitation inception based on bubble dynamics models and change-point detection - Jia Duan; Rongwu Xu; Lilin Cui; Bin Ji; Rui Wu; Heng Liu; Chang Chen (Ocean Engineering, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Partial nitrification achievement through co-regulation of quorum sensing-mediated boric acid and free ammonia - Xu-Ming Liu; Bai-Hang Zhao; Hai-Shan Yang; Rui-Xuan Liu; Lei-Yue Wu (Journal of Water Process Engineering, 2025)

Spatial and temporal variability in molecular characteristics of dissolved organic matter in a large freshwater lake: A case from the Dongting Lake, central China - Rui Xu; Yao Du; Tianming Wu; Xinrui Jiang; Baisong Deng; Mengze Li; Yiqun Gan; Mengjie Song; Shaobo Liao; Rui Zhang; Yanxin Wang (Journal of Hydrology, 2025)

Multiplex immunochromatographic assay for simultaneous detection of triclosan, triclocarban and chlorophene in environmental samples - Jiaxun Li; Lingling Guo; Shanshan Song; Rui Gao; Hua Kuang; Chuanlai Xu; Liguang Xu (Journal of Hazardous Materials, 2025)

Enhancing NO3− reduction on BiFeO3/Cu cathode via ferroelectric polarization: A novel strategy for surface electronic structure regulation - Hao Chen; Houfen Li; Yue Zhao; Yunlong Ma; Zhichao Liu; Rui Li; Sufang Wang; Aijuan Zhou; Xiuping Yue; Haibing Meng; Hongtao Yu; Xu Zhao (Journal of Environmental Management, 2025)

Blast-induced fracture mechanisms and fragmentation characteristics of brittle materials under anisotropic stress fields - Yuanquan Xu; Ming Tao; Rui Zhao; Lei Huang; Haibo Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Gas permeability characteristics and pore structure evolution of sandstones with high-temperature damage effects - Jiang-Feng Liu; Hong-Yang Ni; Xu Chen; Shi-Jia Ma; Zhi-Peng Wang; Rui-Nian Sun (International Journal of Rock Mechanics and Mining Sciences, 2025)

Reed pyrolysis system using multi-stage quench scheme for furfural and chemical production: Process analysis and life cycle assessment - Juntian Xu; Hongmin Pan; Shaomin Zhou; Lan Haijin; Lulu Zhan; Saige Wang; Rui Li; Yulong Wu (Fuel, 2025)

Controlled aggregation of whey protein toward the exceptional tolerance of high ionic strength upon heating - Rui Zhang; Bowen Zou; Junwei Zhang; Xiaokang Na; Xianbing Xu; Ming Du; Beiwei Zhu; Chao Wu (Food Chemistry, 2025)

Cryoprotective activity of different characterized fractions isolated from sea cucumber intestinal protein hydrolysates against salmon - Zhe Xu; Shuang Guan; ShengAo Cao; Rui Zhang; Hanxiong Liu; Zijin Qin; Xiufang Dong; Jianping Wu; Tingting Li (Food Chemistry, 2025)

Fermented Sargassum hemiphyllum soluble dietary fiber exhibits enhanced bioactivity and gut microbiota regulation potential in C57BL/6 mice - Hongying Cai; Zhuo Wang; Rui Li; Qiaoli Zhao; Bingbing Song; Xiaofei Liu; Riming Huang; Baojun Xu; Shouchun Liu; Kit-Leong Cheong; Saiyi Zhong (Food Bioscience, 2025)

Mechanism of dual-pathway peroxymonosulfate activation via Co-Nx coordination-regulated broad-pH-adaptive carbon aerogel for ciprofloxacin degradation - Linjin Li; Jun Wang; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Junyan Li; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Xiaofei Li; et al. (Environmental Research, 2025)

Simultaneous stabilization of high-concentration multi-heavy metal(loid)s co-contaminated soil using Fe/Mn (hydr)oxide-humic acid composites:A novel approach towards sustainable environmental remediation - Rui Xu; Chenyang Yin; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Yan Zhang; Yongbin Yang; Tao Jiang (Environmental Research, 2025)

Core microbiota with antimonite oxidation coupled nitrogen fixation traits persist in the rhizosphere of pioneer plants in antimony tailings - Hanbing Gao; Zhaohui Guo; Fenglian Huang; Shikai Li; Xiao He; Jaovola Ulrich Fernio; Wei lv; Ling Zhou; Shuyang Du; Min Shen; Rui Xu (Environmental Research, 2025)

Unraveling long-term health dynamics of impounded lakes integrating water diversion-adapted planktonic index of biotic integrity and machine learning - Xing Hou; Dawei Wang; Xiaodong Hu; Yi Li; Huanjun Zhang; Lihua Niu; Rui Huang; Jixiong Xu (Environmental Research, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Air pollution, drought, and their synergistic effects on cardiovascular disease risk in China: a nationwide study - Chaohao Ling; Rui Li; Qian Shen; Lulu Cui; Mangen Yang; Zhou Liu; Tianzhao Xu; Wenwen Sun; Shaofu He (Environmental Pollution, 2025)

Road safety performance of a new W-beam guardrail system with rubber sandwich layer under vehicle collisions: Experimental and numerical studies - Zongwang Xie; Rui Wang; Hui Zhao; Shuo Xu; Wensu Chen; Junjun Ren (Engineering Structures, 2025)

A novel single-input single-output system described by transformation function for damage quantification of soft story - Kangqian Xu; Miao Cao; Songtao Xue; Rui Zhang; Xianzhi Li; Zhuoran Yi; Liyu Xie (Engineering Structures, 2025)

Does urban agglomeration lead to energy transition? Evidence from China - Rui Yang; Hang Xu (Energy and Buildings, 2025)

A novel interpolation method for high temporal-resolution electricity usages based on volatility quantification and pattern extraction - Yinao Zhou; Ruoxi Geng; Xuyuan Kang; Huiming Xu; Xiao Wang; Rui Li; Da Yan (Energy and Buildings, 2025)

Removal of insoluble barium scales from reverse osmosis membranes by grafting molecular springs - Xin Wen; Yuyan Hai; Rui Ma; Xu Liang; Yawei Duan; Jingyun Chen; Hui Wei; Rihua Xiong (Desalination, 2025)

Molecular insights into the adsorption behavior of PFAS on montmorillonite, polyethylene, and polypropylene: A molecular dynamics study - Qiao Wang; Rui Xu; Fusheng Zha; Long Xu; Bo Kang; Heming Han (Computers and Geotechnics, 2025)

UV-switchable dual-mode sensing in a lead-free CsCu2I3 perovskite sensor for selective detection of mixed amines - Rui Wu; Qingyi Guan; Mingji Xu; Ruixiang Li; Shu Chen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Interfacial engineering of 0D/3D CeO2/BA nanoarchitectures for highly efficient and selective CO2 photo-reduction to CH4 based on full-spectrum solar-energy utilization - Rui Xu; Chonghai Deng; Chengchen Wang; Yibin Zhu; Yonghui Tong; Zheng Chen; Peipei Sun; LiLi Wang; Lei Yang; Xin Liang; Yiping Wu; Jing Huang; et al. (Chemical Engineering Journal, 2025)

Revealing the differences and similarities in the in-situ and ex-situ activation of VPO catalysts to further optimize the activation process - Jiale Xu; Renjie Ji; Xiaoyu Yan; Rui Huang; Fei Wang; Jianxiang Li; Chunyi Li (Chemical Engineering Journal, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

Gender-specific thermal sensation analysis and SHAP-based prediction across steady, ramp-change, and step-change thermal conditions - Yingle Wei; Jiahua Li; Min Xu; Rui Sun; Fuyuan Xu; Yunsong Han (Building and Environment, 2025)

Changes in gas-to-aerosol-phase partitioning ratio of semi-volatile products affect secondary organic aerosol formation from α-pinene photooxidation - Shijie Liu; Xinbei Xu; Si Zhang; Rongjie Li; Zheng Li; Can Wu; Rui Li; Feiyong Chen; Guiqin Zhang; Gehui Wang (Atmospheric Environment, 2025)

Arabidopsis Dynamin-Related Protein 1a is important for cell plate fusion with parent cell plasma membrane in cytokinesis during pollen mitosis I - Nan Wang; Qingchen Rui; Haoyue Xu; Xiaoyun Tan (Planta, 2025)

Investigation of the mechanism of Dan Zhi Qing’e Formula for treating menopausal hot flashes using UHPLC-Q-TOF MS and network pharmacology - Xinyu Li; Xinyu Liu; Minghui Cai; Shuang Wei; Rui Wang; Nanjian Xu; Jingtian Qu; Yuming Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The m6 A modification of CDKN2 A inhibites ferroptosis and affects the resistance of cervical squamous cell carcinoma to cisplatin - Xiang Yong; Xifeng Xu; Xiaoping Zhang; Rui Song; Huaiyuan Hu; Zhen Li; Yanzi Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Impact of the Combined Application of Zinc and Selenium on the Physiological Mechanisms and Mercury Accumulation in Rice Under Mercury Stress - Qiu Huang; Jing Liu; Wanyu Li; Anqi Xu; Rui Wu; Fanxin Qin (Bulletin of Environmental Contamination and Toxicology, 2025)

Fusarium infection alters the effects of vegetable residue and its compost on nitrous oxide emissions from acid soil - Yumeng Xu; Xiaoxiao Xiang; Waqar Ahmed; Junhui Yin; Owen Fenton; Wenxuan Shi; Jiaqi Wang; Ruixue Chang; Rui Liu; Hao Chen; Guorong Xin; Qing Chen (Applied Soil Ecology, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

A Simplified Prediction Method for the Hydrodynamic Performance of Ship Propellers Under Heave and Pitch Motions - Wei Zhang; Guoliang Xu; Siyu Wang; Rui Wu (Journal of Marine Science and Engineering, 2025)
This paper presents a simplified computational method for evaluating the hydrodynamic performance of a ship propeller, taking into account the effects of wave-induced heave and pitch motions. The method combines Computational Fluid Dynamics (CFD) for propeller hydrodynamic force calculations with forced heave and pitch motions computed via the potential flow theory-based method. Numerical simulations at three representative wavelengths demonstrate that heave and pitch motions reduce propeller thrust, increase torque, and decrease the propeller’s efficiency significantly. In addition, the results reveal a nonlinear coupling between heave and pitch effects, where their hydrodynamic contributions are not simply additive. Compared to high-fidelity ship–propeller coupling CFD simulations, the proposed method reduces computational costs by approximately four times while maintaining practical accuracy for wave–propeller interaction analysis.

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

S-Ketamine Alleviates Anxiety-Induced Chronic Postoperative Pain by Affecting Glucose Metabolism of Striatal Microglia in a Rat Model - Rui Xu; Wei Zhu; Xuan Xu; Yue Yao; Qi Liu; Yan Yang; Yulin Huang; Zhengliang Ma (Journal of Neuroimmune Pharmacology, 2025)

Characteristics and primary controls of coral reef carbonate karstification in the South China Sea since the Miocene - Yang Yang; Kefu Yu; Bin Xiong; Wei Jiang; Shendong Xu; Rui Wang; Tianlai Fan (Frontiers in Marine Science, 2025)
Coral reef karstification plays a vital role in sea-air CO 2 exchange, yet its mechanisms remain unclear. This study employs an 878.22-m coral reef sequence (dating to19.6 Ma) from Well CK2 in the Xisha Islands, South China Sea (SCS), to investigate karstification processes, including their signatures, primary controls, and implications for marine carbonate dissolution in global carbon cycling. Petrological and geochemical analyses of CK2 revel distinct karstification characteristics, including: (1) higher surface porosity 25–30%), with randomly distributed pores and fractures of variable sizes and shapes; (2) yellowish-brown to black impregnations; (3) micritic cements accompanied by well-crystallized mineral crystals, and (4) moderately well-sorted and rounded grains. Geochemical signatures show elevated 8787 Sr/ 86 Sr, Mn content, and Mn/Sr ratios, coupled with depleted δ¹³C, δ 18 O and Sr content. These features collectively indicate that karstification in CK2 was dominated by non-selective dissolution and recrystallization processes, principally occurring at the mixing zone in meteoric water systems during prolonged subaerial exposure. Karstification signatures varied across geological epochs, implying different controlling mechanisms. Late Miocene (12.6–10.2 Ma), driven by sustained sea-level fall, exhibited an extreme 87 Sr/ 86 Sr shift and severe erosion. Pleistocene (2.2–1.8, 1.1–0.89, 0.29 and 0.2 Ma), influenced by frequent sea-level fluctuations and warm, humid environments linked to glacial-interglacial cycle and Asian monsoon, displayed the highest surface porosity (15–40%, mean 25%), ochre to tawny impregnations, and micritized cements, along with negative δ¹³C-δ 18 O and elevated 87 Sr/ 86 Sr and Mn/Sr ratios. In contrast, the Middle Miocene Climatic Optimum (16.6–16 Ma) lacked typical karst characteristics but comprised of well-rounded and sorted coral gravels, suggesting reef-building organisms mediate karstification via substrate architecture. These findings demonstrate that sea-level changes and climate conditions control coral reef karstification intensity. Concurrently, dissolution during karstification may significantly modify ocean alkalinity and dissolved inorganic carbon, with potential feedback on carbon cycling in future climate scenarios.

Suspended solids dominated tailing effect in UV disinfection of livestock wastewater: Mechanistic deciphering and modelling prediction for epidemic control - Wenjing Bai; Jiaojiao Xu; Zhen-Hu Hu; Rui Tang; Xinmin Zhan (Water Research, 2025)

Significant carbon storage and sequestration by urban greenery in Beijing city during 2010–2020 - Junfei Xie; Yang Zhan; Xinyu Li; Ziyun Dai; Richen Cong; Rui Xu; Zhiqi Zhang; Zhisheng Yao (Urban Forestry & Urban Greening, 2025)

Nitric oxide regulates spindle dynamics to modulate the maturation of goat oocytes - Rui Xu; Zhi Zheng; Weizhao Bai; Minghui Liu; Sihai Lu; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2025)

An optimal sequential physical retrieval system for retrieving high-accuracy diurnal atmospheric gases from FY-4B/GIIRS: Theory, algorithm and evaluation - Zhenxing Liang; Dasa Gu; Xin Li; Zijie Xu; Xiangyunong Cao; Heming Bai; Rui Li; Chengxing Zhai; Hui Su; Alexis K.H. Lau (Remote Sensing of Environment, 2025)

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

Effect of geometry of active ignition with turbulent jet ignition on the flame propagation and combustion performance of methanol engine - Diming Lou; Xiaoxiao Zeng; Decheng Wang; Yunhua Zhang; Rui Dong; Yang Xu; Junzhe Li; Xuchong Li; Liang Fang; Yonghong Deng (Process Safety and Environmental Protection, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Data-driven collaborative safety evaluation for seepage reliability of embankments considering spatial variability - Bin Xu; Zichong Liu; Rui Pang; Yang Zhou (Journal of Hydrology, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

Tfh cell-mediated impairment of rotavirus-specific antibodies by PAH and PFAS co-exposure in seropositive children - Jian Zhang; Jieting Chen; Rongyi Kang; Chenxu Dai; Bo Xie; Kaihui Li; Rui Sun; Xiangbin Zheng; Lei Tan; Xijin Xu; Xia Huo (Journal of Hazardous Materials, 2025)

Mg-Al layered double hydroxides derived from secondary aluminum ash for soil remediation contaminated with Cd(Ⅱ) and Cr(Ⅵ) - Shikai Li; Hanbing Gao; Rui Xu; Zhaohui Guo (Journal of Hazardous Materials, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Changes and responses of GPP among different plant functional types in a savanna ecosystem under future climate scenarios - Weiduo Chen; Xuehai Fei; Jingyu Zhu; Rui Chen; Haiqiang Du; Yingqian Huang; Yong Zhang; Yi Shen; Aping Niu; Peng Xu (Journal of Environmental Management, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

From waste tires to enhanced roads: Analysis of performance and emission characteristics of SBS/DRP composite modified asphalt - Mingming Zhang; Wenbo Zhou; Dongwei Cao; Rui Zheng; Lei Xia; Biaozhi Zhang; Qinggang Li; Xu Wang (Journal of Environmental Chemical Engineering, 2025)

Sulfamethazine degradation via PMS activated by Co-Cu catalyst supported on modified geopolymer - Jiayin Liu; Rui Yang; Qi Jiang; Shaobo Chen; Menghao Fang; Shuguang Wang; Zhongjun Xu (Journal of Environmental Chemical Engineering, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Unraveling the impact of coexistent of oxytetracycline and nanomaterials on algal-bacterial granular sludge: Performance, microbial community variations and antibiotic resistance genes - Rui Cheng; Shaowei Hu; Xiaochen Xu; Fenglin Yang (Journal of Environmental Chemical Engineering, 2025)

Selective separation and stepwise recovery of rare earth and aluminum from magnesium salt-based ionic rare earth leaching liquor - Xin Chen; Sihan Ouyang; Zhouyi Chai; Jianfeng Xu; Rui Kang; Yanfei Xiao; Zhifeng Xu (Journal of Environmental Chemical Engineering, 2025)

Surface self-assembly of tannic acid network to enhance wastewater treatment and oil-water separation performance of dual-bismuth BiOBr–BiOCOOH/PVDF membranes - Dong Chen; Rui Zhang; Jie He; Maoqin Xu; Zixi Li; Yujie Liu; Lin Peng (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Elucidating the mechanism by which hofmeister anions influence rheological properties and microstructure of egg yolk low–density lipoprotein/κ–carrageenan double–network hydrogels - Jian Li; Mengzhuo Liu; Yunze Ma; Lina Xu; Huajiang Zhang; Hanyu Li; Lili Zhang; Ning Xia; Rui Chuang; Ahmed M. Rayan; Mohamed Ghamry (Food Hydrocolloids, 2025)

A lytic vibriophage as a potential biocontrol agent against vibriosis in aquaculture - Yunlan Yang; Wanxuan Zhong; Huiyu Ding; Keming Shi; Haipeng Guo; Demin Zhang; Lanlan Cai; Min Hsiao; Jie Xu; Rui Zhang (Fish & Shellfish Immunology, 2025)

Dihydromyricetin switches pyroptosis to apoptosis during Aeromonas hydrophila infection in Mylopharyngodon piceus - Jingjing Xu; Can Yang; Jing Xiang; Rui Song; Dongsheng Ou; Ruozhong Wang (Fish & Shellfish Immunology, 2025)

Benzotriazole (BT) and benzothiazole (BTH) derivatives as emerging marine pollutants in the Pearl River Estuary: Spatiotemporal distribution, environmental fates, and ecological risks - Xiaoxiao Chen; Qianyi Huang; Rui Hou; Shan Liu; Hengxiang Li; Tiantian Chen; Xiangrong Xu (Environmental Pollution, 2025)

Super-resolution for evolutionary probability density of stochastic dynamic responses using physics-guided diffusion model - Zidong Xu; Rui Zhou; Hao Wang (Engineering Structures, 2025)

Utilizing a three-zone control model of adaptive concentrating photovoltaic facade to enhance visual comfort and energy benefits - Bo Wang; Yifan Xu; Hao Wang; Xinshuo Zhang; Yuan Chen; Rui Tang; Ayin Yan; Mengli Zhang; Ying He (Energy and Buildings, 2025)

Subsurface structure of a buried Eratosthenian crater on the far-side of the Moon - Ling Zhang; Chunyang Zhao; Xintong Dong; Shaoping Lu; Yi Xu; Yuqi Qian; Shuo Han; Zhijun Huo; Rui Gao (Earth and Planetary Science Letters, 2025)

Bounding Surface Model for Cyclic Clay Behavior and Its Application in Dynamic Response Analysis of Monopile Offshore Wind Turbines - Kehao Chen; Yang Zhou; Rui Pang; Xingliang Wang; Bin Xu (Computers and Geotechnics, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Closing the loop with citramalic acid-based chiral polyester: A novel strategy as a game-changer for sustainable materials - Lei Song; Xinyu Liu; Ruimin Wang; Mo Zhou; Fei Li; Yunlong Sun; Lu Li; Yanming Hu; Ding Zhou; Xiaowei Xu; Mingyuan Zheng; Rui Wang (Chemical Engineering Journal, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Cascade-targeting hydrogel microspheres with biomimetic nanoparticles enable multifaceted anti-inflammatory and antioxidant defense for osteoarthritis management - Shengli Ma; Yuqiao Sheng; Chaoyang Zhang; Feng Li; Na Wei; Jingjing Xu; Rui Xue (Chemical Engineering Journal, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Achieving stable partial nitrification through AHL-mediated quorum sensing combined with free ammonia: performance, microbial responses, and mechanistic insights - Bai-Hang Zhao; Xu-Ming Liu; Hai-Shan Yang; Rui-Xuan Liu; Lei-Yue Wu (Chemical Engineering Journal, 2025)

ROS-responsive hydrogel loaded with berberine liposome protects against intervertebral disc degeneration by inhibiting mitochondrial fission and apoptosis - Cunliang Guo; Lilong Du; Xiaoxun Du; Rui Gao; Xinyi Jiao; Zhenhua Li; Tongxing Zhang; Pingsheng Huang; Chuangnian Zhang; Zujian Feng; Weiwei Wang; Baoshan Xu (Chemical Engineering Journal, 2025)

Ultrasensitive β12-borophene humidity sensor for intelligent humidity interfaces - Rui Zhu; Zitong Wu; Zhilin Zhao; Maoping Xu; Chuang Hou; Guoan Tai (Chemical Engineering Journal, 2025)

Mechanism of copper (II) speciation influence on cathodic electroactive biofilms in biosensor for groundwater monitoring - Linzhe Huang; Guanlan Wu; Rui Zuo; Chengzhi Wang; Jun Xu; How Yong Ng (Chemical Engineering Journal, 2025)

Global response of soil phosphatase activity to land reclamation and vegetation restoration - Huaisong Wang; Mingming Wang; Jialing Xu; Yibo Tian; Jinyu Bai; Lei Zhang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; Rui Guo; Tao Zhang (CATENA, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Zinc and manganese impact on cabbage (Brassica rapa) cadmium tolerance: comparative transcriptomic and metabolomic study - Wanyu Li; Fanxin Qin; Banglin Luo; Qiu Huang; Anqi Xu; Rui Wu (Plant and Soil, 2025)

Ratiometric core/shell Nanosensors for Simultaneously Measuring Mitochondrial ATP Production and Oxygen Consumption in Living Cells - Rui Jiang; Ying Lian; Enlai Yang; Ying Xu; Jiahao Liang; Yang Yang; Nianhong Wang; Xu-dong Wang (Phenomics, 2025)

Application of platelet-rich plasma lysate combined with hyaluronic acid microneedles for the treatment of alopecia - Zhengxin Suo; Yingcan Xu; Along Zhang; Ye Cao; Jiaxin Liu; Hong Wang; Rui Zhong (Drug Delivery and Translational Research, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Does Water Rights Reform Reduce Water Usage for Agriculture? Evidence From City‐Level Panel Data in China - Hang Xu; Rui Yang (Irrigation and Drainage, 2025)
Existing policies promoting agricultural water conservation focus mainly on promoting water‐saving irrigation through subsidy policies, but this approach leads to a rebound effect, making obtaining the desired water‐saving result challenging. Moreover, many countries have begun to realize that the market‐oriented allocation of water resources through water rights reform (WRR) may be a more effective way of managing water resources to achieve agricultural water conservation. On the basis of the WRR pilot policy in China, this paper uses an empirical difference‐in‐differences (DID) strategy to analyse whether the WRR can reduce agricultural water use. The empirical results show that the WRR can reduce water use by 7% on average, and this result still holds after contemporaneous policies and alternative outcome measures are considered. The possible mechanism is that the WRR has changed the planting structure for food crops and cash‐crops and promoted water resource transfer from the agricultural sector to the non‐agricultural sector. The heterogeneity analysis indicates that the water‐saving effect of WRR is worse in areas with higher land potential or with better economic conditions. Therefore, the promotion of the WRR needs to consider agricultural production conditions and the economic situation.

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Oral bioavailability property prediction based on task similarity transfer learning - Chen Zeng; Chengcheng Xu; Yingxu Liu; Yunya Jiang; Lidan Zheng; Yang Liu; Yanmin Zhang; Yadong Chen; Haichun Liu; Rui Gu (Molecular Diversity, 2025)

High-performance prediction of soil organic carbon using automatic hyperparameter optimization method in the yellow river delta of China - Yingqiang Song; Feng Wang; Weihao Yang; Ruilin Liang; Dexi Zhan; Meiyan Xiang; Xiaohang Yang; Rui Xu; Miao Lu (Computers and Electronics in Agriculture, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

Enhancing the participation of water in the anaerobic digestion of sewage sludge for highly efficient methanogenesis - Jiachang Cao; Ying Xu; Chen Zhang; Xiang Li; Rui Liu; Xueye Wang; Xiaohu Dai (Water Research, 2025)

Sustainable high-flux ceramic membrane operations for seawater pretreatment under diverse algal bloom intensities - Boyan Xu; Meiyue Ding; Kar Ming Tan; Brenda Rui Lin Tan; Tze Chiang Albert Ng; Lai Yoke Lee; Noguchi Hiroshi; Niwa Terutake; Sungwoo Bae; How Yong Ng (Water Research, 2025)

Global ocean surface p CO 2 retrieval and the influence of mesoscale eddies on its performance - Yujie Wang; Yadong Gao; Rui He; Yangyang Gao; Ziyang Xu; Changjie Wang; Fenfen Liu (Science of The Total Environment, 2025)

Efficient solar-driven tandem catalysis for biomass valorization: selective C C bond cleavage to synthesize xylitol - Liangdong Hu; Huiyan Zhang; Zupeng Chen; Nengchao Luo; Lian-Hua Xu; Kai Wu; Longfei Hong; Sheng Chu; Rui Xiao (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

B2G: A novel framework for froth velocity estimation and quantification with graph neural networks - Rui Tian; Ziqi Lv; Xiu Liu; Meijie Sun; Yanan Tu; Zhiqiang Xu; Weidong Wang (Minerals Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Atmospheric transport of microplastics from land to sea is inefficient: Evidence from multimedia observations - Xiangrong Xu; Zhen Yuan; Yanxu Zhang; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Eddy Y. Zeng (Journal of Hazardous Materials, 2025)

Construction and application of a quantitative model for calculating LNAPL lateral migration in the capillary zone - Rui Zuo; Ziyi Wu; Jiawei Liu; Shida Zheng; Zuorong Xu; Zhiwen Wang; Zhenkun Xue; Chengzhi Wang (Journal of Hazardous Materials, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Earthworms mitigate drought effects on microbial decomposition of straw under varying microplastic conditions - Chuanxiong Huang; Weijie Zhao; Hangle Ren; Rui Wu; Ying Liu; Hongxin Xu; Benhua Sun; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Molecular and physiological insights into nicotine degradation by Pseudomonas alloputida Pa_12: Implications for environmental management and tobacco processing - Ang Li; Jie Zhang; Ao Li; Junaid Zafar; Ziling Wan; Yanqing Li; Rui Pang; Fengliang Jin; Xiaoxia Xu (Journal of Cleaner Production, 2025)

Synergistic infrared Co-pyrolysis for integrated resource Recovery: Gas-Induced metal extraction from spent lithium-ion batteries and bio-oil upgrading - Moshan Li; Erfeng Hu; Zuohua Liu; Guangwen Xu; Jianglong Yu; Zhaohui Lu; Guocan Zheng; Dean Pan; Rui Qu (Journal of Cleaner Production, 2025)

Ecological security patterns for coordinating development in frozen soil regions - construction framework by coupling climate change and development objectives - Xiangdong Xu; Xu Yang; Lin Lin; Jingxiao Zhang; Jinggan Shao; Rui Zhi; Tao Feng; Zedong Wang; Yuwen Tang; Junyao Li (Journal of Environmental Management, 2025)

Reconstructing the tectonic evolution of the Mudanjiang Ocean: Metamorphic insights from the Heilongjiang Complex, NE China - Guang-Ming Sun; Xu-Ping Li; Hans-Peter Schertl; Jin-Rui Zhang; Xiao Wang; Wen-Yong Duan (Journal of Asian Earth Sciences, 2025)

Identification of candidate genes engaged in the sex-determination cascade in Eupolyphaga sinensis walker - Rui Zhu; Fei Yang; Tielong Xu (Journal of Asia-Pacific Entomology, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Solar cities: Multiple-reflection within urban canyons - Fan Xu; Man Sing Wong; Rui Zhu; Ying Dang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Microplastics impair black soldier fly bioconversion of pigeon manure: Physiological and transcriptomic insights - Zhimin Xu; Zheng Lin; Runtong Huang; Xueqing Chen; Lei Wang; Xingying Deng; Rui Du; Jiguang Gu; Yifan Wang; Renqiang Yu (International Biodeterioration & Biodegradation, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Sterigmatocystin in rice through LC-MS/MS: Longitudinal study on contamination, health risks and residual patterns in China - Yarong Zhao; Lan Wang; Rui Zeng; Peirong Chen; Kaihang Xu; Xiaomei Huang; Aibo Wu (Food Chemistry, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Antioxidative stress and metabolic regulatory effects of black goji berry anthocyanins from aqueous two-phase extraction in Caenorhabditis elegans - Qiuxiong Xu; Bisheng Zheng; Tong Li; Rui Hai Liu (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

A versatile lignocellulosic sugar platform for green bio-manufacturing featuring high fermentability and diverse lignin valorization - Xiangxue Chen; Zhaoxian Xu; Rui Zhai; Yuanyuan Sha; Shizhong Yang; Meng Qin; Xinchuan Yuan; Mingjie Jin (Chemical Engineering Journal, 2025)

Conduction of AgNPs with different surface charges in pine trees and their prevention and control of pine wood nematode disease - Shouhe Pan; Pengkun Yan; Rui Zhao; Fengyu Li; Lei Wang; Yinmin Wang; Ze Lv; Yingjian Ma; Meng Yu; Xinyu Guo; Yonggang Xia; Yong Xu; et al. (Chemical Engineering Journal, 2025)

Doping potassium to modulate the surface properties of CuO/SiO2 for selective oxidation of isobutane to tert-butanol - Renjie Ji; Jiale Xu; Rui Huang; Xiaoyu Yan; Fei Wang; Chunyi Li (Chemical Engineering Journal, 2025)

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

A novel forward osmosis nanocomposite membrane with g-C3N4 quantum dots fabricated on polyacrylonitrile electrospun nanofiber membrane for high-permeability and selectivity - Dibakar Pandaya; Jia-Rui Yang; Zhen-Liang Xu; Mateen Hedar; Ming-Xiao Zhang; Rui Jia; Rui Han; Muhammad Irfan; Liang Cheng; Mahesh Kumar Joshi (Chemical Engineering Journal, 2025)

Gradient distribution of trap states in polymer dielectrics induced by electric field for enhanced insulation properties - Bing Xia; Ming-Xiao Zhu; Zhi-Hao Xing; Rui Liu; Jie-Rui Ren; Xue-Kai Xu (Chemical Engineering Journal, 2025)

Monolayer graphene interlayer enhanced flexible gas sensor with fast response and high strain tolerance for wearable ammonia monitoring - Chen Wang; Ziran Wang; Feng Xu; Luyang Zhang; Haoyu Yuan; Zaiyu Zhang; Chaqi Gai; Zhongjing Ren; Haipeng Wang; Rui You; Peng Yan (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Spatial confinement of Bi/TiO2 nanoparticles with an abundant heterointerface in hollow carbon spheres for durable sodium storage - Zhao Li; Rui Yuan; Yangwu Hou; Xinde Wei; Zhaozhao Zhu; Yamei Wang; Shilong Xu; Lei Chen; Yan Wang; Rui Wu; Qingquan Kong; Jun Song Chen (Chemical Engineering Journal, 2025)

Harnessing native nitrogen in lignocellulosic biomass for cellulosic ethanol production by ancestral xylose isomerase-engineered Saccharomyces cerevisiae - Kang Yan; Muzi Li; Xingwang Ma; Sitong Chen; Boning Ding; Juncheng Huo; Rui Zhai; Yuanyuan Sha; Zhaoxian Xu; Mingjie Jin (Bioresource Technology, 2025)

Customized microbial inoculants enhance rhizosheath functionality and drive ecosystem restoration in desertified grasslands - Qiqi Han; Weimeng Liu; Yingjie Jiang; Pengyuan Yang; Zixuan Wang; Ziyuan Yan; Zhuo Zhang; Rui Xu; Hui Tang; Guixia Liu (Plant and Soil, 2025)

Structural changes and Cd immobilization mechanism of Solanum nigrum pectin in root and leaf cell walls under Cd stress - Yue Teng; Huibo Sun; Yi Xiao; Jiawei Hu; Rui Xu; Longteng Zhi; Hongyan Yu (Plant and Soil, 2025)

Effect of fulvic acid on aggregate characteristics and humus composition in saline-alkali soil - Rui Cai; Yaru Guo; Yanjie Li; Ling Li; Susu Xu; Ping Gong; Pengfei Li; Hongguang Liu (Plant and Soil, 2025)

The degradation of lignin and cellulose in typhoon-induced unsenescent leaf litter depends greatly on functional strategies among tree species - Rui Cao; Huaibin Wang; Lifeng Wang; Zhuang Wang; Zhihui Wang; Qin Wang; Naiyue Lv; Xu Wang; Wanqin Yang (Plant and Soil, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Dynamic Transcriptome Analysis Uncovers Key Regulatory Genes During Stem Elongation Stages in Wheat - Rui Cao; Yaoyu Chen; Hongyong Dai; Zhencheng Xie; Lifen Wu; Zhan Li; Yuxin Yang; Lichao Zhang; Xu Liu; Xiuying Kong; Chuan Xia (Journal of Plant Growth Regulation, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

MLWNNR: LncRNA-Disease Association Prediction with Multi-Kernel Learning-Driven Weighted Nuclear Norm Regularization - Guo-Bo Xie; Hao-Jie Xu; Guo-Sheng Gu; Zhi-Yi Lin; Jun-Rui Yu; Rui-Bin Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Sequence of middle-lower Ordovician in Shunbei area of Tarim Basin, China, and its geological significance - Rui Xiong; Heng Fu; Yong Li; Caizhu Xie; Ronggang Wang; Shaoze Zhao; Chuan Xu; Chongyang Xiao (Carbonates and Evaporites, 2025)

Experimental and numerical investigation of gas preferential flow through geosynthetic clay liner overlap joint in landfill final cover system - Lin Qin; Fusheng Zha; Rui Xu; Songyu Liu; Abdelmalek Bouazza; He Huang; Qiao Wang (Bulletin of Engineering Geology and the Environment, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

MOF-on-MOF nanomaterial (Fe-MOF@UiO-66)-based ratiometric fluorescence/colorimetric dual-mode sensor for ultrasensitive detection of uric acid - Tao Lian; Rui Peng; Zhengyue Xiao; Xiaomin Tang; Peng Xu; Yu Hu; Ping Qiu (Analytica Chimica Acta, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

Assessment and transferability analysis of soil total nitrogen with different particle sizes based on proximal hyperspectral imaging - Minyi Zhao; Zhentao Wang; Guoqing Chen; Zhenyang Lv; Rui Xu; Yanling Yin; Jinfeng Wang (Computers and Electronics in Agriculture, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Temporal and spatial feature extraction using graph neural networks for multi-point water quality prediction in river network areas - Hang Wan; Long Xiang; Yanpeng Cai; Yulei Xie; Rui Xu (Water Research, 2025)

Algal diversity: A key driver of nitrogen immobilization by phototrophic biofilms at soil-water interfaces in paddy fields - Junzhuo Liu; Rui Sun; Ying Xu; Sichu Wang; Yonghong Wu (Science of The Total Environment, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Dietary Houttuynia cordata Thunb. extract supplementation influences on antioxidant enzymes, meat quality, and gene expressions in fresh rabbit Longissimus thoracis et lumborum meat - Xu Wang; Shuanglong Xie; Rui Chen; Jixiao Qin; Yiqing Xu; Chao Ban; Qi Lu; Xingzhou Tian (Meat Science, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Micro(nano)plastics (< 4 μm): An important but ignored concern during intravenous infusion - Penghui Li; Haoming Xu; Qingcun Li; Yujian Lai; Sujuan Yu; Rui Liu; Bintian Zhang; Jingfu Liu (Journal of Hazardous Materials, 2025)

Bifunctional collagen fibers-based porous material for integrated purification of oily seawater - Xiaoliang Ding; Yejun Yan; Zhexuan Gu; Rui Shi; Yaxin Wang; Guoxin Xu; Zhijun Hu; Zhicheng Jiang (Journal of Hazardous Materials, 2025)

Spatial-temporal evolution pattern, driving mechanism and prediction of dietary sustainability in China - Rui Zhao; Xia Li; Qiang Ren; Zhenci Xu; Fengting Li (Journal of Cleaner Production, 2025)

The influence of sauerkraut fermentation wastewater on nitrogen retention during the composting of garden waste: Focusing on the regulation of the abundance of core microorganisms in the cooling stage - Rui Xu; Xu Wang; Ying Zhang; Xiaoting Song; Gang Song; Wenxiang Ping (Journal of Environmental Management, 2025)

Available medium and micronutrients in the soils of major citrus-producing areas in Southeast China - Zhangqian Xu; Yuzhou Zhou; Rui Liu; Haojie Cui; Jie Tan; Weijun Zhou; Kai Ouyang (Journal of Environmental Management, 2025)

Comparative in vivo study on the digestion behaviors of three typical saturated dietary fats in Sprague Dawley rats - Jiaying Yan; Yanjun Liu; Yanjun Guo; Rui Xu; Zhan Ye; Yuanfa Liu (Food Research International, 2025)

A self-powered photoelectrochemical sensor based on Cs3Bi2Br9/BiOBr photocathode for acetamiprid detection in vegetables - Kun Xu; Rui Xu; Xuejing Liu; Qin Wei (Food Chemistry, 2025)

Deciphering the molecular mechanisms of oil palm lipid metabolism through combined metabolomics and transcriptomics - Jerome Jeyakumar John Martin; Wen Xu; Xinyu Li; Xiaoyu Liu; Lixia Zhou; Rui Li; Dengqiang Fu; Qihong Li; Hongxing Cao (Food Chemistry, 2025)

Recent advancements in chemometrics based non-destructive analytical techniques for rapid detection of adulterants in milk and dairy products – A review - Rui Xu; Muhammad Zeeshan Adil; Sidra Jabeen; Khansa; Mahwish Tanveer; Sadia Younis; Bakhtawar Shafique; Long Li (Food Control, 2025)

l-theanine alleviates ulcerative colitis by repairing the intestinal barrier through regulating the gut microbiota and associated short-chain fatty acids - Aoxiang Liu; Bin Wang; Minming Wang; Rui Tang; Wei Xu; Wenjun Xiao (Food and Chemical Toxicology, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Thiocyanate degradation by mixed bacterial consortia: Adaptive mechanism in response to thiocyanate stress and metabolic pathway - Xuejiao An; Rui Zhao; Liuwei Wang; Xiaoshuang Xiao; Zihang Xu; Shulin Zhang; Dong Xie; Yao Xiao; Qinghua Zhang (Environmental Research, 2025)

Taxonomic and functional responses of benthic macroinvertebrates to wastewater effluents in the receiving river of ecologically vulnerable karst areas in Southwest China - Rui Nie; Xuming Xu; Peijie Xu; Yisi Zhuge; Tong Zheng; Xiao Yu; Rui Yao; Hongwu Tan; Guoqiang Li; Xiaohui Zhao; Qiang Du (Environmental Research, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance” [Chem. Eng. J. 500 (2024) 156765] - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Iron valence regulates sulfur pollution in livestock manure compost: A multipath strategy of chemical fixation-oxidation and microbial metabolism - Qi Wu; Wenfang Gao; Xu Wang; Rui Sun; Yanjie Jiao; Xiang Li; Zimin Wei (Chemical Engineering Journal, 2025)

Adsorption and diffusion of vapour-phase PFAS in montmorillonite and kaolinite: Effect of moisture content and chain length - Qiao Wang; Rui Xu; Fusheng Zha; Songyu Liu; Huaxiang Yan (Chemical Engineering Journal, 2025)

Wound healing accelerated by stem cell bandage - Yingying Liu; Aman Lv; Jinjie Wu; Xiaoyan Wang; Yang Liu; Pui-In Mak; Rui P. Martins; Ren-He Xu; Yanwei Jia (Chemical Engineering Journal, 2025)

Polycomponent metal-organic frameworks of substituent polydispersion hydroxypropyl-β-cyclodextrin as inhalable drug carrier - Xiaojian He; Huipeng Xu; Xiangyu Zhao; Feng Li; Ningning Peng; Jialong Wang; Wenqiang Hua; Feixiang Wang; Guanghong Xu; Rui Yang; Jiwen Zhang; Li Wu (Carbohydrate Polymers, 2025)

In-situ cascaded and selective bio-preparation of galactose-derived acids from cheese whey powder by the bifunctional regulation of resting-cell catalysis - Xia Hua; Rui Zhang; Yating Hu; Dylan Liu; Yong Xu (Bioresource Technology, 2025)

Construction and analysis of atmospheric visibility and fog-haze datasets in China (2001−2023) based on machine learning models - Haifeng Xu; Wenhui Luo; Jinji Ma; Bing Dong; Cheng Wan; Shijie Zhao; Cheng Dai; Rui Qian; Zhengqiang Li (Atmospheric Research, 2025)

Mesenchymal Stromal Cells and Graft-versus-Host Disease: Preclinical and Clinical Studies - Rui Wang; Jingkang Xiong; Qing Xu; Ya Zhou; Shijie Yang; Qingxiao Song; Xiaoqi Wang; Xi Zhang (Stem Cell Reviews and Reports, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Numerical Modeling of Permeability Sensitivities Based on Characteristics of Heterogeneous Coal Structure Reservoirs - Rui Wang; Kun Zhang; Guofu Li; Liangwei Xu (Natural Resources Research, 2025)

Geochemical Characteristics of Natural Gas in the Upper Permian Reservoir of the Eastern Sichuan Basin, China: Implication of Multiple Sources Mixing - Lu Xu; Rui Liu; Yufeng Tang; Kangbin Zhang; Liang Feng; Xiucheng Tan; Fei Liu; Dingchuan Jiang (Journal of Earth Science, 2025)

Impact of Bacillus Licheniformis supplementation on growth performance, health status, and oxidative stress in male dairy calves during the weaning transition period - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

Regional Wave Spectra Prediction Method Based on Deep Learning - Yuning Liu; Rui Li; Wei Hu; Peng Ren; Chao Xu (Journal of Marine Science and Engineering, 2025)
The wave spectrum, as a key statistical feature describing wave energy distribution, is crucial for understanding wave propagation mechanisms and supporting ocean engineering applications. This study, based on ERA5 reanalysis spectrum data, proposes a model combining CNN and xLSTM for rapid gridded wave spectrum prediction over the Bohai and Yellow Seas domain. It uses 2D gridded spectrum data rather than a spectrum at specific points as input and analyzes the impact of various input factors at different time lags on wave development. The results show that incorporating water depth and mean sea level pressure significantly reduces errors. The model performs well across seasons with the seasonal spatial average root mean square error (SARMSE) of spectral energy remaining below 0.040 m2·s and RMSEs for significant wave height (SWH) and mean wave period (MWP) of 0.138 m and 1.331 s, respectively. At individual points, the spectral density bias is near zero, correlation coefficients range from 0.95 to 0.98, and the peak frequency RMSE is between 0.03 and 0.04 Hz. During a typical cold wave event, the model accurately reproduces the energy evolution and peak frequency shift. Buoy observations confirm that the model effectively tracks significant wave height trends under varying conditions. Moreover, applying a frequency-weighted loss function enhances the model’s ability to capture high-frequency spectral components, further improving prediction accuracy. Overall, the proposed method shows strong performance in spectrum prediction and provides a valuable approach for regional wave spectrum modeling.

Retraction Note to: miR-365b-3p adsorbed by HCG18 inhibits the proliferation and angiogenesis of stomach adenocarcinoma by downregulating STC1 - Hui Li; Jian Song; Rui Hou; Yingdong Cao; Huaili Xu (Molecular & Cellular Toxicology, 2025)

Comparative analysis of phycospheric microbial diversity and metabolome between vegetative and matured conchocelis of Pyropia haitanensis - Rui Zhao; Zenghu Zhang; Fuli Liu; Qikun Xing; Ningning Xu; Wenjie Yan; Xu Gao (Aquaculture, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Carbon-friendly design method of tunnel lining segments based on Pareto optimal analysis - Tao Liu; Hehua Zhu; Yi Shen; Liankun Xu; Yi Rui (Tunnelling and Underground Space Technology, 2025)

A hybrid estimation of distribution algorithm for agile earth observing satellite task scheduling problem - Chunchun Ma; Panxing Huang; Xiaoze Liu; Chu-ge Wu; Rui Xu (Swarm and Evolutionary Computation, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

Genomic and functional characterization of the Pantoea ananatis nfd35 strain, a potential biocontrol agent of anthracnose disease in Trichosanthes kirilowii Maxim - Ziang He; Feng Zhu; Shuzhen Sun; Ying Zhang; Rui Min; Huixiang Yang; Leiming Xu; Dengke Yin; Weifang Xu (Physiological and Molecular Plant Pathology, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Flow behavior and retarding mechanism of LNAPL pollutants in capillary zone - Rui Zuo; Chenxi Huang; Kexue Han; Donghui Xu; Xiao Zhao; Jiawei Liu; Ziyi Wu; Jinsheng Wang (Journal of Hydrology, 2025)

GO-SELEX-enhanced dual-recognition sensor for highly specific detection of azamethiphos - Lingjun Geng; Jingcheng Huang; Haowei Dong; Haifang Wang; Rui Xu; Zhiping Yu; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Journal of Hazardous Materials, 2025)

In Vitro metabolism of six representative organic UV stabilizers (OUVs) in marine fish liver microsomes: Kinetics, mechanisms and bioaccumulation evaluation - Yuchen Wang; Qianyi Huang; Siqi Zhang; Shan Liu; Hengxiang Li; Xiaodong Wang; Yan Wang; Rui Hou; Xiangrong Xu (Journal of Hazardous Materials, 2025)

A chemical method to upcycle waste polypropylene into bitumen compatible modifier by polyol grafting through reactive extrusion - Jingting Lan; Zhen Leng; Ruiqi Chen; Xiong Xu; Rui Li; Fuliao Zou; Zhifei Tan (Journal of Cleaner Production, 2025)

Does carbon market improve ESG performance? Evidence from China - Hang Xu; Rui Yang (Journal of Cleaner Production, 2025)

Cotreatment strategy for hazardous arsenic-calcium residue and siderite tailings via arsenic fixation as scorodite - Rui Su; Xinrong Su; Yanjiao Gao; Xu Ma; Xiaoming Zhao; Xiaoxia Ou; Yubo Cui; Jinru Lin; Yuanming Pan; Shaofeng Wang (Journal of Environmental Sciences, 2025)

Bentonite-goethite composite Colloids: Unraveling the mechanisms of strontium adsorption inhibition in claystone for nuclear waste geologic repositories - Rui Zuo; Zuorong Xu; Guanlan Wu; Jun Liu; Shida Zheng; Jun Xu; Jingchao Liu; Jiawei Liu; Weihai Cai (Journal of Environmental Radioactivity, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

Bioactives derived from egg by-products: Preparation, health benefits, and high-value-added applications - Yue Huang; Rui Chuang; Mengzhuo Liu; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

Mechanistic applications of low-temperature plasma in starch-based biopolymer film: A review - Yanli Guo; Mengzhuo Liu; Rui Chuang; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

Dual-recognition strategy sensor based on GO-SELEX aptamer screening for high-specificity identification of fenthion and its major metabolites in vegetables - Lingjun Geng; Haowei Dong; Qingxia Han; Xue Huang; Jingcheng Huang; Haifang Wang; Rui Xu; Jicheng Zhao; Zhouping Wang; Shijia Wu; Ibrahim A. Darwish; Yemin Guo; et al. (Food Bioscience, 2025)

Enhancement of chickpea protein functionalities through higher-intensity pulsed electric field: Insights into protein aggregations and structural changes - Yongxin Teng; Yabin Wang; Xindong Xu; Rui Wang; Boru Chen; Langhong Wang; Fuchao Zhan; Zhong Han; Yonghui Li; Xiangwei Zhu; Xin-An Zeng (Food Hydrocolloids, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Desensitization of HMX crystals by formation of co-particles with insensitive LLM-105 or FOX-7 - Zhi-Hua Xue; Yiran Zhang; Rui Pu; Ruixuan Xu; Shuang Li; Qi-Long Yan (Chemical Engineering Journal, 2025)

Converting a D-/L lactic acid bacteria to its d-type counterpart via a combined chemical mutagenesis and biosensor screening method, and its application in lignocellulosic biorefinery - Xingwang Ma; Kang Yan; Yuwei Zhang; Xiaoyu Xie; Shujie Zou; Yuanyuan Sha; Rui Zhai; Zhaoxian Xu; Mingjie Jin (Bioresource Technology, 2025)

Wind comfort criteria and numbers of wind directions: the dual impact mechanism on pedestrian wind comfort evaluation in Qingdao, China - Xiaofei Chen; Haoxing Hu; Ziqi Xu; Zifei Wu; Rui Ma; Xingtian Wang (Building and Environment, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Inversion of Stress Redistribution Based on Focal Mechanism Solutions: A Case Study of the Dongtan Coal Mine - Kai Zhan; Hao Luo; Rui Xu; Xiaotao Wen; Cong Wang (Rock Mechanics and Rock Engineering, 2025)

Enhanced Microseismic Event Localization in Coal Mines Using the EDDI-Based Cross-Correlation Stacking Method - Kai Zhan; Xuben Wang; Xiaotao Wen; Rui Xu; Chao Kong; Chao Wang (Rock Mechanics and Rock Engineering, 2025)

Variations in lunar regolith mineralogy along the Chang’e-4, Yutu-2 traverse: Combined effects of ejecta sedimentation and subsequent modification - Zhenxing Zhao; Yazhou Yang; Dijun Guo; Yang Liu; Feng Zhang; Xing Wu; Rui Xu; Zhiping He; Yongliao Zou (Science China Earth Sciences, 2025)

Human dental follicle cell-derived conditioned media enhance periodontal regeneration by regulating the osteogenic differentiation and inflammation of periodontal ligament stem cells and macrophage polarization - Yichen Gao; Xianyi He; Yuyao Deng; Xia Wang; Jie Shen; Wei Xu; Rui Cai; Xiaorong Lan; Junliang Chen; Yun He (Molecular and Cellular Biochemistry, 2025)

Functional shift in soil microbiome with decline in photosynthetic carbon input signifies rapid decrease of soil organic carbon during alpine grassland degradation - Minghua Song; Rui Pang; Yuqiang Tian; Yikang Li; Guiqiang Wang; Xingliang Xu (Biology and Fertility of Soils, 2025)

Study on the dynamic characteristics of hybrid ceramic ball bearings in a horizontal canned motor reactor coolant pump - Xiaohang Chen; Danrong Song; Jinqi Lu; Bo Wei; Rui Xu; Dezhong Wang (Annals of Nuclear Energy, 2025)

Molecular characterization of a novel non-segmented double stranded RNA mycovirus infecting the phytopathogenic fungus Botryosphaeria dothidea - Shunpei Xie; Yanan Zhang; Guoqing Xing; Qinzhou Ma; Yashuang Guo; Rui Zang; Chao Xu; Haiyan Wu; Haiqiang Li; Meng Zhang (Archives of Virology, 2025)

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

Ferroptosis: Disease Associations and Therapeutic Target Exploration - Hailing Wang; Liwei Jia; Rui Yin; Shujun Xu; Xin Meng (Journal of Molecular Neuroscience, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Corrigendum to “Evaluation of the main economic characteristics of a narrow-thallus strain of Neoporphyra haitanensis” [Aquaculture Volume 558: 738395, 15 September 2022] - Rui Zhao; Yan Xu; Kai Xu; Dehua Ji; Changsheng Chen; Wenlei Wang; Chaotian Xie (Aquaculture, 2025)

Competitive adsorption and diffusion of methane and vapor-phase per- and polyfluoroalkyl substances in montmorillonite nano pores: Environmental implications - Rui Xu; Qiao Wang; Fusheng Zha; Jiawei Wu; Bokade Mrunal Sunil Shobha; Devendra Narain Singh (Waste Management, 2025)

Identification of key genes linking bisphenols exposure and breast cancer - Zhen Wang; Meng Cao; Tian Gao; Xinyue Xu; Weihua Yu; Jiangzheng Liu; Rui Liu; Xiaodi Zhang; Fei Li; Chunxu Hai (Toxicology, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Adsorption behavior and mechanism of MnMgAl-layered double hydroxide for the removal of V(V): Experiments and DFT calculation - Chenhui Jin; Jie Yang; Rui Zuo; Wanzi Li; Jinsheng Wang; Jing Xu (Process Safety and Environmental Protection, 2025)

Testing micro-aliquot SGC and LnTn methods for age determination up to 780 ka using coarse K-feldspar grains from Nihewan Basin, northern China - Shengxia Xu; Xue Rui; Yujie Guo; Bo Li (Quaternary Geochronology, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Chemical constituents from the stems of Erythropalum scandens - Qiao-dan Pan; Yuan-he Huang; Li-yang Zhao; Wei-rui Wang; Bing-an Wei; Ying-ying Xu; Xian Wei (Phytochemistry Letters, 2025)

Toxic effects and transcriptome analysis of the early life stages of Larimichthys crocea exposed to the bloom-forming dinoflagellate Alexandrium tamarense - Yongqi Cai; Anglu Shen; Hongtao Liu; Chongfeng Liu; Wantu Xu; Rui Jia (Marine Environmental Research, 2025)

Impact of lithofacies categories on inflection-point behaviors in micro-nano pore-structure evolution: Implications for differential reservoir-forming mechanisms and “sweet-spot intervals” identification for marine gas shales - Wei Yang; Rui Yang; Min Wang; Shujing Bao; Leilei Yang; Haodong Hou; Yan Song; Zhenxue Jiang; Ke Miao; Liang Xu (Marine and Petroleum Geology, 2025)

Efficient identification of antibiotic components in three-dimensional excitation-emission matrix fluorescence spectra via deep learning - Xu Kou; Rui Qiu; Peng Chen; Qinru Wang; Yang Chen; Hongguang Guo (Journal of Water Process Engineering, 2025)

An integrated colorimetric biosensing platform containing microneedle patches and aptasensor for histamine monitoring in seafood - Wenjing Wang; Rui Feng; Kaiyue Wei; Jiashuo Xu; Wenhui Dong; Jiao Li; Jianan Sun; Sai Wang; Xiangzhao Mao (Journal of Hazardous Materials, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Co@Al2O3/C3N4 micro-nano catalysts with photothermal confinement effect for enhanced full-spectrum-solar-light-driven CO2 conversion - Yanan Wang; Qi Yin; Rui Zhang; Jie Ma; Song Xu; Qian Liang; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Hydrogel materials in agriculture: A review - Hanghang Wang; Guangfei Qu; Xinxin Liu; Minjie He; Chenyang Yin; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Intelligently responsive PVDF MF membrane with improved antifouling and easy-cleaning performance for efficient separation of oil-water emulsion - Aida Aibulatova; Lin Yu; Zhen-Liang Xu; Jia-Rui Yang; Rui Jia; Yin-Xin Fang (Journal of Environmental Chemical Engineering, 2025)

Characterization of key aroma-active compounds in Chinese steamed breads by sensory-directed aroma analysis - Huijuan Sun; Yue Duan; Rui Xu; Huanlu Song; Haina Gao; Xu Huang; Wanli Qiang; Ruixue Zhang (International Journal of Gastronomy and Food Science, 2025)

Self-luminescent dual-ligand metal-organic framework based electrochemiluminescence probes for organophosphorus pesticides determination - Zheng Shen; Rui Xu; Guangxian Wang; Haifang Wang; Deyan Xu; JingJing Liu; Guanjie Wang; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Discovery of novel DPP4 inhibitory peptides from egg yolk by machine learning and molecular docking: In vitro and in vivo validation - Yujie Xu; Yiqiao Pei; Zhifu Liu; Peng Tan; Rui Liu; Lulu Chu; Ye Zhang; Wenjie Wang; Hao Wang (Food Chemistry, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Antarctic krill oil phosphatidylcholine alleviates visceral hypersensitivity in irritable bowel syndrome: A lipidomics perspective - Siyan Wu; Yanjun Liu; Mengxue He; Zhan Ye; Rui Xu; Yuanfa Liu (Food Bioscience, 2025)

Elucidating interaction mechanisms of protein and diacylglycerol at the interface on the static storage stability of partially crystalline emulsions through a multiscale approach - Pengkai Xie; Zhen Zhang; Yee-Ying Lee; Rui Xie; Junqi Lai; Shuo Zou; Chin Ping Tan; Yufei Zhang; Ying Huang; Geyang Xu; Yong Wang (Food Hydrocolloids, 2025)

Inhibiting fatty acid-binding protein 4 reverses inflammation and apoptosis in wasp sting-induced acute kidney injury - Ling Li; Hai Yuan; Haoran Li; Rui Cheng; Zilin Zhou; Fengqi Hu; Liang Xu (Food and Chemical Toxicology, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Unveiling the potential supply of cultural ecosystem services on the Qinghai-Tibet Plateau: Insights from tourist hiking trajectories - Sheng Huang; Jiawei Yi; Yunyan Du; Fuyuan Liang; Rui Xu; Nan Wang; Jiale Qian; Wenna Tu; Peixian Luo; Andrew Z.F. Xing (Ecosystem Services, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

β-Cyclodextrin/resistant dextrin induced disparate gelling behaviors of high-protein liquid systems - Junwei Zhang; Ruitao Zhu; Bowen Zou; Xiaohan Zheng; Rui Zhang; Xiaokang Na; Xianbing Xu; Ming Du; Chao Wu (Carbohydrate Polymers, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Deep Learning-Based Surrogate-Assisted Intelligent Optimization Framework for Reservoir Production Schemes - Lian Wang; Hehua Wang; Liehui Zhang; Liang Zhang; Rui Deng; Bing Xu; Xing Zhao; Chunxiang Zhou; Li Fan; Xindong Lv; Junda Wu (Natural Resources Research, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Development of novel caffeic acid derivatives as multifunctional agents for the treatment of AD - Kerong Hu; Jing Yang; Qiyao Zhang; Xinxin Wang; Yujie Xu; Yuxin Zhang; Zhenghuai Tan; Wenmin Liu; Rui Chen; Zhipei Sang (Medicinal Chemistry Research, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Investigation of scale effect on shear behaviors of natural rock joints using the overlapping sampling method - Qinkuan Hou; Shuhong Wang; Rui Yong; Minna Xu; Wenpan Sun; Furui Dong (Bulletin of Engineering Geology and the Environment, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

Effects of dietary Lycium barbarum polysaccharide on the growth, antioxidant, immunity response, and intestinal microbiota in Bulatmai barbel (Luciobarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Wei Xu; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

The sedimentological heterogeneities and responses to controlling factors in Toutunhe Formation of Xiayan Rise, Junggar Basin - Nai-xiang He; Xiang Li; Ya-jie Ding; Rui Qi; Gang Xu; Zi-jian Han; Chao Hou; Lei Xie (Applied Geophysics, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Ginsenoside Rf in wild ginseng adventitious roots extract inhibits melanogenesis via cAMP/PKA and NO/cGMP signalling pathways in α-melanocyte-stimulating hormone-stimulated B16F10 mouse melanoma cells and zebrafish - Hong Chen; Mengqiong Jian; Huanhuan Teng; Zhenzhuo Li; Xiaohao Xu; Xiangzhu Li; Rui Jiang; Daqing Zhao; Liwei Sun; Jianzeng Liu (Natural Product Research, 2025)

Growth monitoring of rapeseed seedlings in multiple growth stages based on low-altitude remote sensing and semantic segmentation - Fanguo Zeng; Rui Wang; Youming Jiang; Zhendong Liu; Youchun Ding; Wanjing Dong; Chunbao Xu; Dongjing Zhang; Jun Wang (Computers and Electronics in Agriculture, 2025)

In-field blueberry fruit phenotyping with a MARS-PhenoBot and customized BerryNet - Zhengkun Li; Rui Xu; Changying Li; Patricio Munoz; Fumiomi Takeda; Bruno Leme (Computers and Electronics in Agriculture, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Research on distributed displacement monitoring and strain inversion assessment methods for buried pipelines in fracture zones - Qunying Fan; Rui Pang; Jiajian Wang; Liang Ren; Bin Xu (Tunnelling and Underground Space Technology, 2025)

Assessment of full-process VOCs emissions of on-road vehicles considering individual parking behaviors - Xinru Yang; Dawen Yao; Rui Xu; Yuzhuang Pian; Shikun Liu; Yonghong Liu (Transportation Research Part D: Transport and Environment, 2025)

AdvUNet3+: Segmentation of city-scale heterogeneous building façade materials from street view images - Jing Kai Daniel Tan; Rui Zhu; Jie Song; Zheng Qin; Yanqing Xu; Yumin Chen (Sustainable Cities and Society, 2025)

Anti-pain effect and mechanism of plant extracts in sensitive skin: A review - Rui Xu; Xianxian Cao; Yonglei Yuan; Liping Qu (South African Journal of Botany, 2025)

Advanced oxidation processes for the removal of artificial sweeteners from aqueous environments: A comprehensive review - Jiayin Liu; Qi Jiang; Shaobo Chen; Rui Yang; Menghao Fang; Zhongjun Xu (Process Safety and Environmental Protection, 2025)

Holocene coral reef carbonate REY geochemistry during the neomorphism from aragonite to calcite: A case study in the South China Sea - Wei Jiang; Yuwen Xiao; Kefu Yu; Rui Wang; Shendong Xu; Ning Guo; Tingwu Gu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A novel Gordonia sp. PS3 isolated from the gut of Galleria mellonella larvae: Mechanism of polystyrene biodegradation and environmental toxicological evaluation - Luhui Xu; Xuejiao An; Huoyong Jiang; Rui Pei; Zelin Li; Jiehao Wen; Wenjie Pi; Qinghua Zhang (Journal of Hazardous Materials, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Fabrication and mechanism of microspheres with tunable and control-released hydrophobicity in a wide-range: Ultra-low-density proppant - Zhenyong Li; Yang Zhou; Da Zhang; Min Xu; Rui Li; Xianyan Ren (Fuel, 2025)

The curvilinear relationship between perceived stress and spicy food craving in Young females: A non-linear mediation effect of positive emotional experience of spicy food consumption - Huizhen Qiu; Yidan Rui; Yuchen Zhang; Meiqi Hu; Shuang Zheng; Nanlin Xu; Jiaqi Jing; Pengfei Han; Hong Chen; Xiao Gao (Food Quality and Preference, 2025)

Design of an injectable magnetic hydrogel with porous structure and electrocatalytic activity for the sensitive electrochemical detection of nitrite in foods - Yongfeng Chen; Shixin Li; Rui Gao; Yujie Shi; Yufeng Sun; Geoffrey I.N. Waterhouse; Zhixiang Xu (Food Chemistry, 2025)

Impact of interfacial rigidity on the rheological properties of high internal phase Pickering emulsions stabilized by casein, walnut protein isolate, and their complexes - Rui Jiang; Yanfei Xu; Zheng Zhou (Food Hydrocolloids, 2025)

Spatiotemporal evolution and risk thresholds of PM2.5 components in China from the human health perspective - Haifeng Xu; Wenhui Luo; Cheng Dai; Shijie Zhao; Rui Qian; Bing Dong; Zhengqiang Li; Jinji Ma (Environmental Pollution, 2025)

Time-series InSAR landslide three-dimensional deformation prediction method considering meteorological time-delay effects - Jichao Lv; Rui Zhang; Xin Bao; Renzhe Wu; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2025)

L-arginine-enhanced PEI-based polyamide Nanofiltration membranes for efficient heavy metal ion removal - Junwei Li; Shan Wang; Qingjuan Zhu; Daliang Xu; Yongmei Wang; Xi Zhang; Jiale Du; Qin Chen; Rui Zhao; Xiang Hu; Yong Liu; Raf Dewil; et al. (Desalination, 2025)

A novel soil reaction model for continuous impact pile driving - Shihong Zhang; Lizhong Wang; Mengtao Xu; Shengjie Rui; Zhen Guo (Computers and Geotechnics, 2025)

Defect-repair in carbon for fast and stable potassium and sodium storage - Rui Ma; Yaxin Chen; Binyuan Zhang; Lili Ai; Changyu Leng; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Hydrogel-elastomer hybrid integrated with radiative and evaporative cooling for passive temperature-adaptive regulation - Libin Sun; Da-Wen Sun; Liang Xu; You Tian; Rui Hu; Zhiwei Zhu (Chemical Engineering Journal, 2025)

Process modeling guided start-up and stable operation of a pilot-scale mainstream partial denitrification-anammox system - Min Xu; Wenbo Chai; Wanlu Zhu; Yuyan Zhang; Rui Xiao; Changzhi Wang; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2025)

Microstructure evolution of SOFC pure Ni anode with carbon deposition under polarization - Dongxu Cui; Ryo Kato; Yosuke Komatsu; Anna Sciazko; Bin Wang; Yue Xu; Shiliang Wu; Dengyu Chen; Rui Xiao; Naoki Shikazono (Chemical Engineering Journal, 2025)

Stimuli-responsive hydrogels composed of modified cellulose nanocrystal and gelatin with oriented channels for guiding axonal myelination - Shuqin Xu; Xiaoli Tang; Maosen Wang; Zhuqun Wang; Rui Zhan; Jinghua Chen (Carbohydrate Polymers, 2025)

Modelling sunlight and shading distribution on 3D trees and buildings: Deep learning augmented geospatial data construction from street view images - Shu Wang; Rui Zhu; Yifan Pu; Man Sing Wong; Yanqing Xu; Zheng Qin (Building and Environment, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Dynamic transcriptomics and physiological insights reveal multi-tissue salt adaptation mechanisms in Amaranthus hypochondriacus across stress gradients - Qian Xu; Jinxin Gan; Zhikang Zhou; Tao Zhou; Rui Lu; Ningfang Liu; Longxing Hu (Plant Cell Reports, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Online monitoring and stable isotope tracing of cancer associated volatiles in murine model captures tumor associated markers in vivo - Fouad Choueiry; Rui Xu; Andrew Gold; Hyein Jung; Jiangjiang Zhu (Analytica Chimica Acta, 2025)

Simulating oasis-desert interactions in artificial and natural oasis-desert areas: Integration of remote sensing data and CFD methodology - Zhixing Peng; Shaomin Liu; Rui Liu; Xinlei He; Jin Ma; Ziwei Xu; Ji Zhou; Dongxing Wu (Agricultural and Forest Meteorology, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Millennial-scale surface hydrological variability in the tropical eastern Indian Ocean linked to Northern Hemisphere high latitudes - Rui Cui; Peng Zhang; Jian Xu; Ann Holbourn; Wolfgang Kuhnt (Frontiers in Marine Science, 2025)
Surface hydrology in the tropical eastern Indian Ocean significantly impacts low-latitude climate processes including the Indonesian-Australian Monsoon and the Indian Ocean Dipole. Deciphering the evolution of surface hydrology and driving mechanisms is thus important to better understand low-latitude and global climate change. Here, we present ~206 yr-resolved temperature and salinity records of surface waters spanning the past ~31 kyr, based on δ 18 O and Mg/Ca ratio of Globigerinoides ruber from Core SO18567 retrieved offshore northwestern Australia in the tropical eastern Indian Ocean. By integrating new records with published paleo-oceanographic and -climatological records, we found that increasing sea surface temperature and decreasing salinity in the tropical eastern Indian Ocean during the Heinrich stadial 1 and the Younger Dryas could be attributed to collapse of the Atlantic Meridional Overturning Circulation (AMOC). Melting of Northern Hemisphere ice sheets would have led to a southward shift of the Intertropical Convergence Zone (ITCZ) and reduced transport of warm surface waters from the low latitudes to the Northern Hemisphere high latitudes. In addition, our results indicate that the onset of the last deglacial warming in low latitudes was linked to weakening of the Hadley circulation and AMOC due to warming of Northern Hemisphere high latitudes, rather than raised global atmospheric CO 2 concentration.

Time-varying compressive mechanical characteristics and empirical model construction of loquat (Eriobotrya japonica Lindl.) based on FEM-RSM - Changsu Xu; Puzan Zhang; Rui Song; Han Tang; Yunwu Li (Computers and Electronics in Agriculture, 2025)

FACNet: A high-precision pumpkin seedling point cloud organ segmentation method - Zerui Liu; Junhong Zhao; Yaowen Hu; Rui Li; Qiaomei Deng; Renxiang Guan; Ruoli Yang; Zhuonong Xu; Guoxiong Zhou (Computers and Electronics in Agriculture, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Dissimilatory nitrate reduction pathways drive high nitrous oxide emissions and nitrogen retention under the flash drought in the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Hongjie Zhang; Junxiang Cheng; Ligang Xu; Qinglong L. Wu; Jin Zeng (Water Research, 2025)

Mitophagy impairment drives microglia activation and results in cognitive deficits in neonatal mice following sevoflurane exposure - Piao Zhang; Rui-Juan Cheng; Qiao-Ling Yang; Yan Gong; Yan Xu; Ling-Min Chen; Li Zhou; Chun-Ling Jiang (Toxicology Letters, 2025)

A learning-based dual-population optimization algorithm for hybrid seru system scheduling with assembly - Yuting Wu; Ling Wang; Rui Li; Yuxiang Xu; Jie Zheng (Swarm and Evolutionary Computation, 2025)

Global rehabilitation research equality index across health conditions during 1990–2019: an alignment analysis between bibliographic and epidemiological data - Xin Guo; Jiakang Huo; Wanwei Dai; Tong Wang; Han Xiao; Wenjing Zhao; Xuanyu Shi; Xueheng Wang; Yang Gao; Zhi Li; Rui Zhan; Wenli Xu; et al. (Science Bulletin, 2025)

Global analysis and prediction of the occurrence and fate of PFASs in dumpsites - Rui Xiang; Guangyuan Yao; Can Qian; Yuqiang Liu; Ya Xu; Qifei Huang (Resources, Conservation and Recycling, 2025)

Targets selection and field evaluation of an RNA biopesticide to control Phyllotreta striolata - Saibo Xu; Xuezhi Zhang; Yinuo Wang; Rui Han; Xuexia Miao; Haichao Li; Ruobing Guan (Pesticide Biochemistry and Physiology, 2025)

Effect and mechanism of the moisture content on the kinetic retardation of LNAPL pollutant migration by the capillary zone - Kexue Han; Rui Zuo; Ronggao Qin; Donghui Xu; Xiao Zhao; Minghao Pan; Jiawei Liu; Yunxiang Xu; Jinsheng Wang (Journal of Hazardous Materials, 2025)

Study on the effect of surfactant ethoxy content on the wettability adjustment of bituminous coal interface - Lei Fang; Jiangshi Zhang; Yunfei Liang; Linquan Tong; Jianguo Liu; Hongfu Jia; Xinyang Chen; Pengcheng Liu; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Microwave-assisted synthesis and functionalization of biochar for environmental remediation: Regulate strategy and application potential - Jianhua Qu; Rui Yu; Xiaoyang Liu; Wei Peng; Fuxuan Bi; Xu Liu; Qiwen An; Yupeng Zhang; Qi Hu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Synthesis and performance evaluation of hydrate dissociation inhibitors suitable for cementing hydrate formations - Yuhuan Bu; Zilong Lu; Chang Lu; Huajie Liu; Shenglai Guo; Hexing Liu; Rui Ma; Zhen Zhang; Mengran Xu (Fuel, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Solar-driven transient Lewis acid sites for synergistic efficient photocatalytic isomerization of glyceraldehyde - Liangdong Hu; Lian-hua Xu; Chenjun Yang; Longfei Hong; Kai Wu; Sheng Chu; Longlong Ma; Shurong Wang; Rui Xiao; Huiyan Zhang (Chemical Engineering Journal, 2025)

NIR-activatable proenzyme DSF/CuS@M for synergistic in situ chemotherapy/CDT/PTT/cuproptosis-based antitumor therapy - Lushuang Xu; Qinyue Chen; Yangwei Qian; Jin Wang; Chenxi Wang; Rui Fan; Jia-Wei Shen; Qiying Shen (Chemical Engineering Journal, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Highly efficient separation of anthracene and carbazole in crude anthracene by composite extractants with low viscosity - Yuanyuan Wang; Wenhai Zhang; Danting Wang; Rui Ma; Lili Ai; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang; Hong Meng (Chemical Engineering Journal, 2025)

High-throughput screening method for glycolipids based on substrate modification and their efficient biomanufacturing - Yuanyi Li; Zhilin Liu; Yiming Zheng; Ke Sun; Peng Lei; Yian Gu; Yongting Song; Jian Xue; Weidong Cai; Rui Wang; Hong Xu; Liang Sun (Bioresource Technology, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Driving analysis and prediction of COD based on frequency division - Mei Li; Kexing Chen; Deke Wang; Yilin He; Rui Xu (Stochastic Environmental Research and Risk Assessment, 2025)

Unraveling Neurotoxicity Discrepancies: Comparative In vitro and In vivo Analysis of Colistin and Polymyxin B and the Underlying Mechanisms - Rui Yang; Debiao Xiang; Fang Yuan; Yuan Yang; Pengkai Wang; Bing Xu; Xin Li (Molecular Neurobiology, 2025)

Fatty acid binding protein 4 knockdown improves fetal development in rats with gestational diabetes mellitus through modulating autophagy mediated by the PTEN/Akt/mTOR signaling pathway - Fanglei Yang; Yifan Mao; Bin Tang; Rui Xu; Feiyun Jiang (Journal of Molecular Histology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Pharmacological Inhibition of TXNRD1 by a Small Molecule Flavonoid Butein Overcomes Cisplatin Resistance in Lung Cancer Cells - Rui Yang; Shibo Sun; Qiuyu Zhang; Haowen Liu; Ling Wang; Yao Meng; Na Chen; Zihan Wang; Haiyan Liu; Fengyun Ji; Yan Dai; Gaohong He; et al. (Biological Trace Element Research, 2025)

Influence mechanism of the non-uniform inflow on flow characteristics of horizontal reactor coolant pump - Jinqi Lu; Xiaohang Chen; Danrong Song; Rui Xu; Dezhong Wang (Annals of Nuclear Energy, 2025)

Knockdown of SETD5 Inhibits Colorectal Cancer Cell Growth and Stemness by Regulating PI3K/AKT/mTOR Pathway - Xiaohua Zhou; Wenqiang Chen; Duanming Zhuang; Guangqi Xu; Yongqiang Puyang; Hongqing Rui (Biochemical Genetics, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Development of a Mitochondrial Marker for Distinguishing Between Ulva linza and Ulva prolifera - Rui Zhai; Chengnuo Tang; Shuying Wang; Jing Ma; Xinshu Li; Guoqiang Chen; Juntian Xu (Journal of Marine Science and Engineering, 2025)
The green tide is the biggest ecological disaster in Yellow Sea in recent decades, and the species composition has varied from year to year. The ITS (internal transcribed spacer) sequence combined with 5S rDNA spacer are the mainstream molecular markers for green macroalgae. The former can perfectly distinguish the majority of Ulva spp. except the LPP (Ulva linza–procera–prolifera) complex, and the latter is used to distinguish U. linza and U. prolifera exactly based on the former. However, in practice, 5S rDNA spacer is difficult to amplify perfectly with universal primers, and this ultimately affects the experimental process. For this reason, we developed a stable mitochondrial marker for the distinction between U. linza and U. prolifera. The phylogenetic tree based on the mitochondrial rps2 (ribosomal protein S2) gene fragment can distinguish the LPP complex into two clades: U. linza and U. prolifera. Therefore, we concluded that the mitochondrial marker can be a great substitute for 5S primers to distinguish U. linza and U. prolifera.

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

Weakly supervised dual-mask marginal segmentation and variable path planning method for bean weed based on UAV remote sensing - Jianlin Zhang; Xiangyu Lu; Rui Yang; Hongxing Xu; Yan Huai; Fei Liu (Computers and Electronics in Agriculture, 2025)

Introducing PES porous membrane to establish bionic autocrine channels: A lubricating, anti-wear antifouling coating - Rui Zhao; Jine Wang; Zhe Cheng; Lianglong Zou; Meihua Jin; Jiujun Xu (Marine Pollution Bulletin, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Engineering crop performance with upstream open reading frames - Rui Mou; Ruixia Niu; Ruoying Yang; Guoyong Xu (Trends in Plant Science, 2025)

Reactivation of critically-stressed basement faults and related induced seismicity in the southeastern Sichuan basin - Mengke An; Rui Huang; Derek Elsworth; Fengshou Zhang; Zhen-Yu Yin; Liuke Huang; Zhengyu Xu (Tectonophysics, 2025)

Meta-Black-Box optimization for evolutionary algorithms: Review and perspective - Xu Yang; Rui Wang; Kaiwen Li; Hisao Ishibuchi (Swarm and Evolutionary Computation, 2025)

Effect of rhizosphere soil microenvironment interaction on ginsenoside content in Panax ginseng: A case study of three-year-old agricultural ginseng - Zhefeng Xu; Yuqiu Chen; Rui Liu; Yibing Wang; Chunshuo Liu; Jing Fang; Qinghe Zhang; Tao Zhang; Changbao Chen (Rhizosphere, 2025)

Separation and degradation techniques for microplastics in soil environments - Yifan Xu; Panting Zhang; Rui Zhang; Chengtun Qu; Ying Yuan; Kunlong Hui; Jie Sun; Wenbing Tan (Journal of Water Process Engineering, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Co-exposure to polystyrene nanoplastics and F-53B induces vascular endothelial cell pyroptosis through the NF-κB/NLRP3 pathway - Junli Lv; Zhenzhen Tan; Ziwen An; Rui Xu; Huaxing Zhang; Mingmei Guo; Fang Xiao; Mengwei Zhao; Yi Guo; Yi Liu; Xuehui Liu; Jingtao Ma; et al. (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Biochar chemical-looping gasification for hydrogen-rich syngas production in solid-solid reaction: O, H and CaO of carbide slag effect NiFe2O4 oxygen carrier - Chenlong Liu; Wenqiang Tang; Xuechen zhang; Siddig Abuelgasim; Chenghua Xu; Rui Liu; Hengyi Xie; Fan Jiang (Journal of Environmental Management, 2025)

Effect of radio frequency combined oven pretreatment on the drying characteristics and quality of sweet potatoes - Qingqing Jiao; Xiangyu Guan; Juanjuan Xu; Li Liu; Rui Li; Yinfa Yan; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Structural evolution of Ni-Ce bimetallic alloy on Al2O3 support in methane dry reforming: Achieving sustainability and high-efficiency reaction through cerium modulation strategy - Xu Ma; Wei-Wei Yang; Jia-Rui Zhang; Xin-Yuan Tang (Fuel, 2025)

Microwave pyrolysis of food waste: Kinetics, bio-oil characteristics, and formation mechanisms of N-containing components based on DFT calculations - Donghua Xu; Junhao Lin; Rui Ma; Shichang Sun (Fuel, 2025)

Directed substitution and evolution of active sites in quaternary ammonium resin catalyst for oxalate transesterification - Hongbin Xia; Yuxin Wang; Rui Xia; Xinyang Xiong; Guangwen Xu; Jinggang Zhao; Jun Zhou; Lei Shi (Fuel, 2025)

Fat substitute in salad dressing: The role of soybean oil body self-aggregates in enhancing texture and rheological property - Xiaoyu Li; Rui Liu; Xin Lv; Ikram Alouk; Shuai Chen; Wenlu Li; Song Miao; Yanbo Wang; Duoxia Xu (Food Research International, 2025)

Structural characteristics and antioxidant activity of binary compounds formed by covalent modification of plant derived recombinant lactoferrin (OsrhLF) with four typical carbohydrates - Xiaoyan Guan; Kexin Wang; Yeting Wu; Jing Xu; Rui Liu; Zixian Xia; Yanchun Shao; Youyou Lu (Food Chemistry, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Biochar@MIL-88A(Fe) accelerates direct interspecies electron transfer and hydrogen transfer in waste activated sludge anaerobic digestion: Exploring electron transfer and biomolecular mechanisms - Weihang Xu; Lan Wu; Mengqi Geng; Junmei Zhou; Sai Bai; Duc Viet Nguyen; Rui Ma; Di Wu; Jin Qian (Environmental Research, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Biofouling evolution driven by autoinducer-2 quorum sensing in reverse osmosis (RO) for water reclamation - Huijuan Xu; Seonki Lee; Rui Yun Chia; Tzyy Haur Chong (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Dual-targeting of PDPN-expressing synovial fibroblasts and macrophages via CLEC-2-engineered exosomes for osteoarthritis therapy - Bo Yu; Rui Peng; Zitao Liu; Shanchuang Chen; Nanjun Xu; Qingjun Yang; Zhengang Zha; Bolai Chen; Tao Jiang; Tao Gui; Songwei Huan (Chemical Engineering Journal, 2025)

Highly selective ppb-level Cl2 sensor at room temperature based on ZIF-8 coated MIL-68(In)-derived hexagonal tubes - Sumin Wang; Rui Gao; Ming Zheng; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Xin Zhou; Lihua Huo (Chemical Engineering Journal, 2025)

A photoswitchable phase-reversible gel engine for systemic redox homeostasis remodeling and on-demand chemodynamic immunotherapy with sustainable immunostimulation - Minghao Sun; Weiwei Liu; Yuanyuan Ma; Pengfei Ni; Wenjing Yao; Yingjie Xu; Rui Bao; Jue Wang; Fei Xiong; Xihe Kuang; Teng Zhang; Xiaochen Zhang; et al. (Chemical Engineering Journal, 2025)

Zinc-doped nickel sulfide/nickel hydroxide heterostructures for efficient and robust selective glucose oxidation reaction - Chi Zhang; Chunjian Xu; Linrui Yang; Xinyue Tao; Jianyi Liu; Rui Su; Xiangjun Meng; Ruoxi Yang; Dongfang Xue; Kaitian Zheng (Chemical Engineering Journal, 2025)

Molecular cation passivation and bromine vacancy supplement strategy for efficient wide-bandgap perovskite solar cells - Yue Yu; Maoxia Xu; Rui Liu; Haorong Ren; Jiangzhao Chen (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

GFFMNet: Prediction Method for Coal Mine Seismic Focal Mechanisms Based on GCN - Kai Zhan; Xigui Zheng; Rui Xu; Cong Wang; Ping Song (Rock Mechanics and Rock Engineering, 2025)

Bayesian Microseismic Localization Method Based on the Maximum Entropy Hamiltonian Monte Carlo Markov Chain Approach - Kai Zhan; Xuben Wang; Xiaotao Wen; Rui Xu; Chao Kong; Chao Wang (Rock Mechanics and Rock Engineering, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

PKS1 involved in anthocyanin accumulation in red-skinned pear fruit - Lei Guo; Yuting Hao; Ying Tang; Mengjia Wu; Rui Zhai; Chengquan Yang; Lingfei Xu; Zhigang Wang (Plant Cell Reports, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Sodium-glucose cotransporter 2 inhibitors and contrast-induced nephropathy risk: a meta-analysis - Gang Fan; Lin Lin; Hong Zuo; Rui Yan; Chao Xu (European Journal of Clinical Pharmacology, 2025)

A new oviraptorosaur from the Lower Cretaceous Miaogou Formation of western Inner Mongolia, China - Mingze Hao; Zhiyu Li; Zhili Wang; Shuqiong Wang; Feimin Ma; Qinggele; J. Logan King; Rui Pei; Qi Zhao; Xing Xu (Cretaceous Research, 2025)

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Wheat Fusarium head blight severity grading using generative adversarial networks and semi-supervised segmentation - Guoqing Feng; Ying Gu; Cheng Wang; Dongyan Zhang; Rui Xu; Zhanwang Zhu; Bin Luo (Computers and Electronics in Agriculture, 2025)

Assessment of the bioflocculant production and safety properties of Metabacillus hrfriensis sp. nov. based on phenotypic and whole-genome sequencing analysis - Rui Zhang; Zhigang Zhao; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Aquaculture, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Chicken adipose tissue is differentially involved in primary and secondary regional immune response to NDV through miR-20a-5p-NR4A3 pathway - Yi Jiang; Rui Zhang; Xinxin Xu; Xiangnan Wang; Yufei Tian; Wei Zhang; Xiaoli Ma; Chaolai Man (Veterinary Immunology and Immunopathology, 2025)

Leveraging machine learning to explore nonlinear associations between urban heat vulnerability and morbidity risk - Jiaming Yang; Zhaomin Tong; Jiwei Xu; Rui An; Yanfang Liu; Yaolin Liu (Urban Climate, 2025)

Identifying publicly perceived high temperature thresholds across Chinese cities using geotagged social media data - Rui Xu; Jiawei Yi; Wei Qi; Yunyan Du; Sheng Huang; Nan Wang; Jiale Qian; Wenna Tu; Dingchen Hu; Ting Ma; Ashraf Dewan (Sustainable Cities and Society, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

First investigation of the luminescence dating of loess in the eastern Tibetan Plateau using K-feldspar MAR MET-pIRIR protocol - Li Liu; Shengli Yang; Pushuang Li; Jingzhao Zhang; Rui Li; Dongxue Li; Xuechao Xu; Yuanlong Luo; Xiuyun Yang (Quaternary Geochronology, 2025)

Alkaloids from Dendrobium nobile and their anti-inflammatory activities - Zao-Yu Xu; Chao-Fan Wang; Wen Li; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Transboundary cooperation potential under climate change and hydropower development in the Dulong-Irrawaddy river basin: A perspective on the water-energy-food-ecosystem nexus - Ziyue Xu; Kai Ma; Jiwei Leng; Kaiwen Zhang; Rui Luo; Daming He (Journal of Cleaner Production, 2025)

Mixotrophic denitrification using thiocyanate as an electron donor: Role of thiocyanate under different C/N conditions - Zhuocheng Wei; Bin Zhang; Rui Xu; Haoling Li; Acong Chen; Chaohai Wei; Haizhen Wu (Journal of Environmental Management, 2025)

The impact of water rights reform on economic development: Evidence from city-level panel data in China - Hang Xu; Rui Yang (Journal of Environmental Management, 2025)

Adsorption characteristics and mechanism insights of K2FeO4 coupling with ZnCl2-assisted modified functionalized biochar for Pb (II) in wastewater - Xuewen Yang; Fulin Yang; Can Liu; Hao Sun; Defa Hou; Yunwu Zheng; Hui Gao; Rui Shi; Xiahong He; Xu Lin (Journal of Environmental Chemical Engineering, 2025)

Improvement of ecological structure and function in phosphorus tailings-based soils through phosphorus-solubilizing bacteria inoculation and magnetic field treatment - Caiyue Jin; Xinxin Liu; Bangjin Chen; Guangfei Qu; Yaxin Tian; Fenghui Wu; Jieqian Yang; Rui Xu; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

The role of sulfur cycle in new particle formation: Cycloaddition reaction of SO3 to H2S - Haijie Zhang; Wei Wang; Liang Fan; Junling Li; Yanqin Ren; Hong Li; Rui Gao; Yisheng Xu (Journal of Environmental Sciences, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

Plant polyphenols as natural bioactives for alleviating lipid metabolism disorder: Mechanisms and application challenges - Haiying Wei; Jinsheng Rui; Xinke Yan; Ruyan Xu; Simeng Chen; Baiming Zhang; Lei Wang; Zhisong Zhang; Chengwen Zhu; Mengtao Ma; Huining Xiao (Food Research International, 2025)

Preparation strategy of molecularly imprinted polymers adsorbent based on multifunctional carrier for precise identification and enrichment of fenthion - Lingjun Geng; Jingjing Liu; Jingcheng Huang; Haifang Wang; Peisen Li; Rui Xu; Chengqiang Li; Haowei Dong; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Methodology for quality risk prediction for milk powder production plants with domain-knowledge-involved serial neural networks - Kaiyang Chu; Rui Liu; Xu Shen; Guijiang Duan (Food Chemistry, 2025)

From a metabolomics profiling perspective explaining the deterioration impact induced by chicken meat exudate - Ruilin Xu; Rui Ding; Xuankai Zheng; Junhua Shao; Xinglian Xu; Xue Zhao (Food Chemistry, 2025)

Ascorbic acid treatment inhibits early wound healing in the fresh-cut potato by relegating jasmonic acid biosynthesis and signal transduction - Fuhui Zhou; Rui Ma; Dongying Xu; Aili Jiang (Food Chemistry, 2025)

Novel time-resolved fluorescent-based multiplex immunochromatography test strip for simultaneous detection of pesticides in vegetables - Zhengtao Li; Haowei Dong; Haifang Wang; Donghan Li; Shuxian Zhou; Shengxi Zhai; Jingcheng Huang; Rui Xu; Wenping Zhao; Mohamed Bedair M. Ahmed; Gili Bisker; Xia Sun; et al. (Food Chemistry, 2025)

Utilization of egg white powders to mitigate the astringency of Aronia berry juice and produce protein-Proanthocyanidin aggregates with enhanced stability during digestion - Rui Huang; Xiaoqing Xie; Changmou Xu (Food Chemistry, 2025)

Radio frequency inactivation of Bacillus cereus and natural microbiota in brown rice: Evaluation of inactivation kinetics and germination capacity - Gaoji Yang; Dingting Zhou; Juanjuan Xu; Yingqi Tian; Rui Li; Shaojin Wang (Food Control, 2025)

Construction of low-toxicity cadmium sulfide/nitrogen-doped muti-walled carbon nanotubes for peroxymonosulfate activation: The crucial role of electron transfer - Jin Qian; Sai Bai; Mengqi Geng; Dandan Zhang; Guoping Xiang; Yichu Zhang; Yangju Li; Dongdong Chu; Di Wu; Rui Ma; Yueping Bao; Xiangning Xu; et al. (Environmental Research, 2025)

Multifunctional composites made from waste polyester cotton fabric and waste rigid polyurethane foam for potential building wall material applications - Feng Liang; Qinxian Chen; Zhen Shi; Rui Dan; Huan Liang; Xu Feng; Chuanyun Tang; Xijing Yu; Xianqin Shang; Denglu Zhang; Yuanyuan Hu (Energy and Buildings, 2025)

Up-concentration of organic matter from municipal wastewater by coagulation coupled with active coke adsorption to improve carbon capture and anaerobic methanogenesis efficiency - Ying An; Yanhua Xu; Chen Tang; Xingzhi Du; Zihang Ma; Rui Tang; Bin Zhou; Zhan Qiu; Zhen Zhou (Chemical Engineering Journal, 2025)

Recent progress in Cu-based electrocatalysts for CO2 reduction - Ruo-Zheng Xiong; Hui-Min Xu; Hong-Rui Zhu; Zhi-Jie Zhang; Gao-Ren Li (Chemical Engineering Journal, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

A multifunctional biosensor for selective identification, sensitive detection and efficient photothermal sterilization of Salmonella typhimurium and Staphylococcus aureus - Huasong Dai; Yingyue Zhang; Wenshi Zhao; Rui Guo; Sihan Qian; Yang Xu; Yuxuan Li; Yang Liu; Hongbo Liu (Analytica Chimica Acta, 2025)

The STING signaling pathways and bacterial infection - Jiayi You; Ailing Xu; Ye Wang; Guangmin Tu; Rui Huang; Shuyan Wu (Apoptosis, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Underwater Target Detection with High Accuracy and Speed Based on YOLOv10 - Zhengliang Hu; Le Cheng; Shui Yu; Pan Xu; Peng Zhang; Rui Tian; Jingqi Han (Journal of Marine Science and Engineering, 2025)
Underwater target detection exhibits extensive applications in marine target exploration and marine environmental monitoring. However, conventional images of underwater targets present challenges including blurred contour information, complex environmental conditions, and pronounced scattering effects. In this work, an underwater target detection method based on YOLOv10 is designed, and the detection performance is compared with the YOLOv5 model. Experimental results demonstrate that the YOLOv10 model has a mAP50 of 85.6% on the URPC 2020 dataset, improving the mAP50 by 1.2% than that of YOLOv5. This model exhibits high detection accuracy and high proceeding speed, which provides a promising support for precise and fast underwater target detection.

From Genes to Metabolites: HSP90B1’s Role in Alzheimer’s Disease and Potential for Therapeutic Intervention - Cheng Huang; Ying Liu; Shuxin Wang; Jinjun Xia; Di Hu; Rui Xu (NeuroMolecular Medicine, 2025)

A high-available segmentation algorithm for corn leaves and leaf spot disease based on feature fusion - Falin Guo; Caihua Yao; Rui Yang; Miaomiao Ma; Xiaojiang Wu; Zihan Xu; Ming Lu; Jie Zhang; Guoshu Gong (Crop Protection, 2025)

Biodegradation of organic micropollutants by anoxic denitrification: Roles of extracellular polymeric substance adsorption, enzyme catalysis, and reactive oxygen species oxidation - Siqi Xu; Rui Li; Yang Liao; Jiyong Bian; Ruiping Liu; Huijuan Liu (Water Research, 2025)

Complicated pollution characteristics (particulate matter, heavy metals, microplastics, VOCs) of spent lithium-ion battery recycling at an industrial level - Rui Wang; Akemareli Bulati; Lu Zhan; Zhenming Xu (Science of The Total Environment, 2025)

To kill or to piggyback: Switching of viral lysis-lysogeny strategies depending on host dynamics - Chen Hu; Xiaowei Chen; Wei Wei; Douglas Wallace; Jihua Liu; Yao Zhang; Lianbao Zhang; Dapeng Xu; John Batt; Xilin Xiao; Qiang Shi; Qiang Zheng; et al. (Science of The Total Environment, 2025)

Migration modeling of metal(loid)s in soil-groundwater systems from an abandoned mine: Based on multimethod integration - Chiyue Huang; Zhaohui Guo; Rui Xu; Chi Peng (Science of The Total Environment, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Numerical investigation on the suction caisson response considering seabed trenches and cyclic loading - Le Wang; Tingran Zhang; Xinglei Cheng; Wanhai Xu; Zhichao Shen; Shengjie Rui; Yinghui Tian (Ocean Engineering, 2025)

Formate enhances partial-denitrification and energy production by anammox bacteria in simultaneous anammox-denitrification system - Min Xu; Rui Xiao; Huijie Lu (Journal of Water Process Engineering, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Interval prediction of fuel cell degradation based on voltage signal frequency characteristics with TimesNet-GPR under dynamic conditions - Wenchao Zhu; Yongjia Li; Yafei Xu; Leiqi Zhang; Bingxin Guo; Rui Xiong; Changjun Xie (Journal of Cleaner Production, 2025)

Noble gases in Paleozoic shale fluids document tectonic events and fluid migration in the Upper Yangtze Block - Rui Liu; Tao Wen; Daniele L. Pinti; Rui Xu; Fang Hao; Shang Xu; Zhiguo Shu (International Journal of Coal Geology, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

A facile colorimetric sensor for ketoprofen detection in milk: Integrating molecularly imprinted polymers with Cu-doped Fe3O4 nanozymes - Yu Su; Xinjie Yin; Xiaofeng Wei; Rui Xu; Liwen Wei; Yanhua Chen; Lan Ding; Daqian Song (Food Chemistry, 2025)

Potential interventions and interactions of bioactive polyphenols and functional polysaccharides to alleviate inflammatory bowel disease – A review - Muhammad Salman Farid; Bakhtawar Shafique; Rui Xu; Łukasz Łopusiewicz; Changhui Zhao (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Role of a noval amadori rearrangement product: N- (1-deoxy-D-fructos-1-yl) -γ-aminobutyric acid in changing the taste of Huangjiu - Gang Han; Zhilei Zhou; Rui Chang; Qingxi Ren; Zhongwei Ji; Xibiao Xu; Yuezheng Xu; Jian Mao (Food Bioscience, 2025)

Mitochondrial protective effects of black goji berry anthocyanins in Caenorhabditis elegans: Defenses against oxidative stress - Qiuxiong Xu; Bisheng Zheng; Tong Li; Rui Hai Liu (Food Bioscience, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

Alleviates effects of γ-cyclodextrin/genistein inclusion complex on oxidative stress injury induced by organic hydrogen peroxide in PC12 cells via Nrf2/GPx4 signaling pathway - Mengmeng Zhang; Jingbo Liu; Yiding Yu; Wenshuo Ren; Rui Yuan; Xuanting Liu; Xiaomin Shang; Zhiyang Du; Meng-Lei Xu; Ting Zhang (Food Bioscience, 2025)

Peptidomics and computational peptidology insights into the taste peptide profile of different extraction methods: A case study of fermented rice wine (Huangjiu) - Rui Chang; Zhilei Zhou; Yuezheng Xu; Xibiao Xu; Zhongwei Ji; Shuangping Liu; Jian Mao (Food Bioscience, 2025)

Oil unsaturation degree dictates emulsion stability through tuning interfacial behaviour of proteins - Weiyi Zhang; Rui Zheng; Xinglian Xu; Xue Zhao (Food Hydrocolloids, 2025)

Regulatory effects and mechanism of different selenium species on cadmium accumulation in Triticum aestivum L. (microbial response, gene expression and element accumulation) - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Environmental Research, 2025)

Poly-γ-glutamic acid chelates chromium (III) and copper (II), alleviating their toxicity in cucumber and affecting rhizosphere bacterial community assembly - Chaoyang Chen; Wenhui Yan; Yu Chen; Sijie Liu; Chuanjiang Nong; Liang Sun; Rui Wang; Hong Xu; Peng Lei; Yian Gu (Environmental Pollution, 2025)

Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xiaoqing Xu; Hongfa Luo; Bin Wang; Yuqing Liu; Kaixiang Miao; Rui Hao; Weiwei Lin; Yuwen Zhou; Dongyang He; Md Asadujjaman (Engineering Structures, 2025)

Evaluation of the shear stiffness and load redistribution of framed structures affected by tunnelling - Jingmin Xu; Zehui Yu; Rui Chen; Tao Xu; Churong Chen; Ziqi Wang (Computers and Geotechnics, 2025)

Regulating inner Helmholtz plane by partial carbonization nano-dots additive for reversible zinc metal anode - Hongji Xu; Rui Gao; Linglong Hu; Meihua Zhu; Ze Gao; Zhongjun Chen; Siqi Meng; Dongxue Chu; Ming Feng (Chemical Engineering Journal, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Molecular level modulation of anthracite-based hard carbon precursors for efficient sodium-ion batteries - Rui Li; Chunbo Su; Wei Yang; Ruizhe Xu; Kai Chen; Jian Chen; Wei Su; Beilei Yuan; Jianping Long; Anjun Hu (Chemical Engineering Journal, 2025)

Sandwich-like NiFe-LDH/MnCO3/MXene ternary nanocomposites serve as battery-type electrode for high-performance asymmetric supercapacitor - Liangchen He; Ping Cai; Huajun Lai; Kecheng Lu; Zebing Xu; Rui Zeng; Chenggang Hao; Zhongmin Wang; Weijiang Gan (Chemical Engineering Journal, 2025)

Ultrafine Na3V2(PO4)3@C with boosted interfacial charge transfer kinetics for low-temperature (−40 °C) Na-ion battery - Yanjing Liu; Shitan Xu; Huacheng Zhu; Yang Yang; Yang Yang; Yanping Zhou; Xianhong Rui (Chemical Engineering Journal, 2025)

Unsteady hydrate film controlled mechanism of rapid hydrate formation: From pilot to pore scales - Xuan Kou; Heng Zhang; Xiao-Sen Li; Kun Wan; Rui Xu; Yi Wang (Chemical Engineering Journal, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

Exceptional mechanical strength and superior vibration damping characteristics in a super biomass diaphragm - Rui Yang; Anran Dong; Linghui Qi; Honggang Xu; Jinxuan Jiang; Liping Cai; Jiamin Wu; Tao Ding; Changlei Xia; Jianzhang Li (Chemical Engineering Journal, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

Preparation and structural characterization of a sulfated octasaccharide with heparin-like anticoagulant activity - Ning Yu; Rui Fang; Zhao Ding; Xi Xu; Jianfa Zhang (Carbohydrate Polymers, 2025)

Precipitation events and long-term nitrogen addition synergistically stimulate heterotrophic respiration in a semi-arid meadow steppe - Tianhang Zhao; Xu Yang; Rui He; Junqin Li; Wenzheng Song; Yanan Li; Baoku Shi; Weifeng Gao; Wei Sun (CATENA, 2025)

Carbon translocation within land snails affects the carbon isotopic fractionation - Chenglong Li; Haolin Tan; Min Wu; Rui Bao; Yijiang Xu; Xuefen Sheng (Chemical Geology, 2025)

Enhancing lead tolerance in spirulina using glycine betaine under high CO2 and salinity for sustainable carbon capture - Chunli Yu; Rui Xu; Shengxi Shao; Wenguang Zhou (Bioresource Technology, 2025)

Production of α-amylase from gluconate and carbon dioxide by protein synthesis and secretion optimization in Cupriavidus necator H16 - Ruohao Tang; Rui Xu; Xuemin Gao; Cunxi Dai; Xiaochun Qin; Jianming Yang (Bioresource Technology, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

A Method for Coal Mine Seismic Network Detection Capability Calculation Based on Energy - Kai Zhan; Xiaotao Wen; Cong Wang; Chao Kong; Chao Wang; Rui Xu (Rock Mechanics and Rock Engineering, 2025)

Protective effect of SERCA2a-SUMOylation by SUMO-1 on diabetes-induced atherosclerosis and aortic vascular injury - Jinlin Liu; Shifang Xu; Bin Gao; Meng Yuan; Li Zhong; Rui Guo (Molecular and Cellular Biochemistry, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

A fidelity evaluation model for watermarked vector maps based on improved fuzzy comprehensive evaluation and random forest - Xu Xi; Huimin Tian; Jinglong Du; Mingkang Wu; Rui Huang (Earth Science Informatics, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Nanozymes featuring a mesoporous silica shell for rapid enrichment and ultrasensitive lateral flow immunoassay of influenza A - Jing Liang; Xiaoxian Liu; Zhenzhen Liu; Xuanming Xu; Yinuo Sun; Yuan Chen; Rui Xiao; Yajie Wang (Analytica Chimica Acta, 2025)

Phase residuals analysis in kinematic orbit determination of GRACE-FO - Rui Zhang; Yongliang Xiong; Shaoguang Xu (Advances in Space Research, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)